JP2017100366A - Resin laminate and method for producing the same - Google Patents

Resin laminate and method for producing the same Download PDF

Info

Publication number
JP2017100366A
JP2017100366A JP2015235714A JP2015235714A JP2017100366A JP 2017100366 A JP2017100366 A JP 2017100366A JP 2015235714 A JP2015235714 A JP 2015235714A JP 2015235714 A JP2015235714 A JP 2015235714A JP 2017100366 A JP2017100366 A JP 2017100366A
Authority
JP
Japan
Prior art keywords
meth
layer
resin
film
cured coating
Prior art date
Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
Pending
Application number
JP2015235714A
Other languages
Japanese (ja)
Inventor
英人 山澤
Hideto Yamazawa
英人 山澤
宏 岡藤
Hiroshi Okafuji
宏 岡藤
Current Assignee (The listed assignees may be inaccurate. Google has not performed a legal analysis and makes no representation or warranty as to the accuracy of the list.)
Mitsubishi Chemical Corp
Original Assignee
Mitsubishi Chemical Corp
Mitsubishi Chemicals Holdings Corp
Priority date (The priority date is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the date listed.)
Filing date
Publication date
Application filed by Mitsubishi Chemical Corp, Mitsubishi Chemicals Holdings Corp filed Critical Mitsubishi Chemical Corp
Priority to JP2015235714A priority Critical patent/JP2017100366A/en
Publication of JP2017100366A publication Critical patent/JP2017100366A/en
Pending legal-status Critical Current

Links

Landscapes

  • Laminated Bodies (AREA)
  • Addition Polymer Or Copolymer, Post-Treatments, Or Chemical Modifications (AREA)

Abstract

【課題】反射防止機能、帯電防止機能、防眩機能及び汚れ防止機能等の機能層を有し、表面硬度、耐擦傷性、密着性及び耐クラック性に優れた樹脂積層体及びその製造方法を提供する。【解決手段】樹脂基材の少なくとも一方の面に、8Hの鉛筆硬度を有する特定の硬化被膜(A)、及びウレタン(メタ)アクリレート由来の繰り返し単位及びアミノ基を有する(メタ)アクリレート由来の繰り返し単位の少なくとも1種類を含む硬化被膜(B)が順に形成された樹脂積層体。前記樹脂積層体の硬化被膜(B)は、反射防止機能、帯電防止機能、防眩機能及び汚れ防止機能から選ばれる少なくとも一つの機能を有することができる。或いは又、前記樹脂積層体は、前記硬化被膜(B)の表面に、前述した機能を有する機能層(C)をさらに積層することができる。【選択図】 なしA resin laminate having a functional layer such as an antireflection function, an antistatic function, an antiglare function and a dirt prevention function, and having excellent surface hardness, scratch resistance, adhesion and crack resistance, and a method for producing the same provide. A specific cured coating (A) having a pencil hardness of 8H, a repeating unit derived from urethane (meth) acrylate, and a repeating unit derived from (meth) acrylate having an amino group on at least one surface of the resin substrate. The resin laminated body in which the cured film (B) containing at least 1 type of a unit was formed in order. The cured coating (B) of the resin laminate can have at least one function selected from an antireflection function, an antistatic function, an antiglare function, and a stain prevention function. Or the said resin laminated body can further laminate | stack the functional layer (C) which has the function mentioned above on the surface of the said cured film (B). [Selection figure] None

Description

本発明は、樹脂積層体及びその製造方法に関する。さらに詳しくは、8Hの鉛筆硬度を有する硬化被膜の表面に、反射防止機能、帯電防止機能、防眩機能及び汚れ防止機能から選ばれる少なくとも一つの機能を有する機能層が形成された樹脂積層体及び該樹脂積層体の製造方法に関する。   The present invention relates to a resin laminate and a method for producing the same. More specifically, a resin laminate in which a functional layer having at least one function selected from an antireflection function, an antistatic function, an antiglare function, and an antifouling function is formed on the surface of a cured film having a pencil hardness of 8H, and The present invention relates to a method for producing the resin laminate.

従来、液晶テレビ及び携帯電話等のディスプレイを保護するためのディスプレイ用前面板として、透明性を有する樹脂シートに対する需要がある。透明性の高い樹脂シートには、反射防止機能、帯電防止機能、防眩機能及び汚れ防止機能等の機能にくわえて、耐擦傷性や高い表面硬度等の性能が要求されている。 Conventionally, there is a demand for a resin sheet having transparency as a display front plate for protecting displays such as liquid crystal televisions and mobile phones. Highly transparent resin sheets are required to have performances such as scratch resistance and high surface hardness in addition to functions such as an antireflection function, an antistatic function, an antiglare function, and an antifouling function.

樹脂シートの表面硬度、耐擦傷性等を向上させる手法として、例えば、特許文献1には、特定の多官能(メタ)アクリレート単量体と特定のウレタン(メタ)アクリレート単量体を含む活性エネルギー線硬化性組成物を硬化させてなる硬化被膜が開示されている。   As a technique for improving the surface hardness, scratch resistance, etc. of the resin sheet, for example, Patent Document 1 discloses an active energy containing a specific polyfunctional (meth) acrylate monomer and a specific urethane (meth) acrylate monomer. A cured coating obtained by curing a linear curable composition is disclosed.

特許文献2には、耐擦傷性、表面硬度、汚れ防止機能を有する樹脂シートにさらに防眩機能を付与する手法として、透明プラスチックフィルム基材の表面に活性エネルギー線硬化樹脂と光拡散性粒子を含有する光拡散層を形成した光学フィルムが開示されている。   In Patent Document 2, an active energy ray curable resin and light diffusing particles are applied to the surface of a transparent plastic film substrate as a technique for further imparting an antiglare function to a resin sheet having scratch resistance, surface hardness, and antifouling function. An optical film having a light diffusing layer contained therein is disclosed.

また、ハードコート層(硬化被膜)の表面に各種機能層を積層して、樹脂積層体の耐擦傷性と表面硬度を両立する技術として、特許文献3には、樹脂基材の表面に帯電防止層及び低屈折率層を順に積層した樹脂積層体が開示されている。   In addition, Patent Document 3 discloses an antistatic technique on the surface of a resin base material, as a technique for laminating various functional layers on the surface of a hard coat layer (cured coating) to achieve both scratch resistance and surface hardness of the resin laminate. A resin laminate in which a layer and a low refractive index layer are sequentially laminated is disclosed.

また、特許文献4には、樹脂基材の表面に、アミノシランを含む高屈折率膜、低屈折率膜がこの順で積層された樹脂積層体が開示されている。   Patent Document 4 discloses a resin laminate in which a high refractive index film containing aminosilane and a low refractive index film are laminated in this order on the surface of a resin base material.

樹脂積層体の表面硬度を満足させる手法として、特許文献5には、樹脂基材の表面に、特定の多官能単量体を含む硬化被膜を積層した樹脂積層体が開示されている。   As a technique for satisfying the surface hardness of the resin laminate, Patent Document 5 discloses a resin laminate in which a cured film containing a specific polyfunctional monomer is laminated on the surface of a resin base material.

特開2009−114,248号公報JP 2009-114,248 A 特開2007−114,760号公報JP 2007-114,760 WO2006/132,180号公報WO2006 / 132,180 publication WO2012/086,749号公報WO2012 / 086,749 WO2014/184,983号公報WO2014 / 184,983 publication

しかしながら、特許文献1、特許文献2に開示されている技術では、樹脂シートの耐擦傷性は向上するが、表面硬度が十分ではない。 However, with the techniques disclosed in Patent Document 1 and Patent Document 2, the scratch resistance of the resin sheet is improved, but the surface hardness is not sufficient.

特許文献3に開示されている技術では、樹脂積層体の基材と帯電防止層の界面強度(層間接着力)が十分ではない。   In the technique disclosed in Patent Document 3, the interface strength (interlayer adhesive force) between the base material of the resin laminate and the antistatic layer is not sufficient.

特許文献4に開示されている技術では、樹脂積層体の耐擦傷性、各層間の密着性は向上するが、表面硬度が十分ではない。   In the technique disclosed in Patent Document 4, the scratch resistance of the resin laminate and the adhesion between the layers are improved, but the surface hardness is not sufficient.

特許文献5に開示されている技術では、樹脂積層体の表面硬度は向上するが、樹脂積層体の最外層である硬化被膜の表面に、反射防止層、帯電防止層、防眩層及び汚防層等の機能層をそのまま積層すると、硬化被膜と機能層の密着性が十分でない。   In the technique disclosed in Patent Document 5, the surface hardness of the resin laminate is improved, but an antireflection layer, an antistatic layer, an antiglare layer, and an antifouling layer are formed on the surface of the cured film that is the outermost layer of the resin laminate. When a functional layer such as a layer is laminated as it is, the adhesion between the cured film and the functional layer is not sufficient.

本発明はこれらの問題点を解決することを目的とする。すなわち、本発明は、反射防止機能、帯電防止機能、防眩機能及び汚れ防止機能等の機能層を有し、表面硬度、耐擦傷性、密着性及び耐クラック性に優れた樹脂積層体を提供することを目的とする。   The present invention aims to solve these problems. That is, the present invention provides a resin laminate having functional layers such as an antireflection function, an antistatic function, an antiglare function, and an antifouling function and excellent in surface hardness, scratch resistance, adhesion and crack resistance. The purpose is to do.

本発明の第1の要旨は、樹脂基材の少なくとも一方の表面に、鉛筆硬度8H以上の硬化被膜(A)を備え、硬化被膜(A)における樹脂基材と接する面と対向する面に硬化被膜(B)を備えたシート状の樹脂積層体である。前記硬化被膜(B)は、ウレタン(メタ)アクリレート由来の繰り返し単位(b2−1)及びアミノ基を有する(メタ)アクリレート由来の繰り返し単位(b2−2)の少なくとも1種類を含むことが好ましい。前記硬化被膜(A)の膜厚が17μm以上40μm以下が好ましい。また、前記硬化被膜(B)は、低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層から選ばれる1つの機能を有する層を用いることができる。前記樹脂積層体の表面の鉛筆硬度は8H以上が好ましい。   The first gist of the present invention is that a cured coating (A) having a pencil hardness of 8H or more is provided on at least one surface of a resin substrate, and the cured coating (A) is cured on a surface facing the surface in contact with the resin substrate. It is a sheet-like resin laminate provided with a coating (B). The cured coating (B) preferably contains at least one of a repeating unit (b2-1) derived from urethane (meth) acrylate and a repeating unit (b2-2) derived from (meth) acrylate having an amino group. The film thickness of the cured coating (A) is preferably 17 μm or more and 40 μm or less. The cured coating (B) may be a layer having one function selected from a low refractive index layer, a high refractive index layer, a hard coat layer, an antistatic layer, an antiglare layer and an antifouling layer. The pencil hardness of the surface of the resin laminate is preferably 8H or more.

本発明の第2の要旨は、第1の要旨の樹脂積層体の硬化被膜(B)の表面に、低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層から選ばれる少なくとも1つの機能を有する層からなる機能層(C)を設けた、樹脂積層体である。前記樹脂積層体の表面の鉛筆硬度は8H以上が好ましい。   The second gist of the present invention is that a low refractive index layer, a high refractive index layer, a hard coat layer, an antistatic layer, an antiglare layer and an antiglare layer are formed on the surface of the cured film (B) of the resin laminate of the first gist. It is a resin laminate provided with a functional layer (C) composed of a layer having at least one function selected from a dirty layer. The pencil hardness of the surface of the resin laminate is preferably 8H or more.

本発明の第3の要旨は、樹脂基材の少なくとも一方の表面に、硬化被膜を備え、硬化被膜(A)における樹脂基材と接する面と対向する面に硬化被膜(B)を備えたシート状の樹脂積層体である。前記硬化被膜(A)が、分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(a1)、分子中に2個以下の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(a2)を含む。また、前記硬化被膜(B)は、ウレタン(メタ)アクリレート単位(b2−1)及びアミノ基を有する(メタ)アクリレート単位(b2−2)の少なくとも1種類を含む。前記硬化被膜(A)の膜厚が17μm以上40μm以下が好ましい。前記硬化被膜(A)の鉛筆硬度は8H以上が好ましく、前記樹脂積層体の表面の鉛筆硬度は8H以上が好ましい。   The third gist of the present invention is a sheet comprising a cured coating on at least one surface of a resin substrate, and a cured coating (B) on the surface facing the surface in contact with the resin substrate in the cured coating (A). It is a resin-like laminated body. The cured coating (A) has a repeating unit (a1) derived from a monomer having 3 or more (meth) acryloyloxy groups in the molecule, and a single unit having 2 or less (meth) acryloyloxy groups in the molecule. The repeating unit (a2) derived from a monomer is included. Moreover, the said cured film (B) contains at least 1 sort (s) of the urethane (meth) acrylate unit (b2-1) and the (meth) acrylate unit (b2-2) which has an amino group. The film thickness of the cured coating (A) is preferably 17 μm or more and 40 μm or less. The pencil hardness of the cured coating (A) is preferably 8H or higher, and the pencil hardness of the surface of the resin laminate is preferably 8H or higher.

本発明の第4の要旨は、下記工程(1)及び工程(2)を含む樹脂積層体の製造方法にある。   The 4th summary of this invention exists in the manufacturing method of the resin laminated body containing the following process (1) and process (2).

工程(1):樹脂基材の少なくとも一方の表面に、分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(a1)、分子中に2個以下の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(a2)を含む硬化被膜(A)を形成する。 Step (1): A repeating unit (a1) derived from a monomer having 3 or more (meth) acryloyloxy groups in the molecule on at least one surface of the resin substrate, and 2 or less (meta ) A cured coating (A) containing a repeating unit (a2) derived from a monomer having an acryloyloxy group is formed.

工程(2):前記硬化被膜(A)の表面に、ウレタン(メタ)アクリレート単位(b2−1)及びアミノ基を有するメタクリレート単位(b2−2)の少なくとも1種類を含む硬化被膜(B)を形成する。 Step (2): A cured film (B) containing at least one kind of urethane (meth) acrylate unit (b2-1) and methacrylate unit (b2-2) having an amino group on the surface of the cured film (A). Form.

前記工程(2)の硬化被膜(B)の形成は、硬化被膜(A)の表面に、分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体(b1)と、ウレタン(メタ)アクリレート単量体(b2−1)及びアミノ基を有する(メタ)アクリレート単量体(b2−2)の少なくとも1種類(ただし、単量体(b1)を除く)と、有機溶剤(b4)を含む硬化性組成物(s1)の塗膜を形成し、硬化して、硬化被膜(B´)とする方法を用いることができる。   In the step (2), the cured film (B) is formed on the surface of the cured film (A) by the monomer (b1) having 3 or more (meth) acryloyloxy groups in the molecule and urethane (meta ) At least one of acrylate monomer (b2-1) and (meth) acrylate monomer (b2-2) having an amino group (excluding monomer (b1)), and organic solvent (b4) A method of forming a cured coating film (B ′) by forming a coating film of the curable composition (s1) containing, and curing it can be used.

本発明の第5の要旨は、第4の要旨の製造方法の工程(2)の硬化被膜(B)を形成する工程が、前記硬化被膜(A)の表面に、分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体(b1)、及びウレタン(メタ)アクリレート単量体(b2−1)及びアミノ基を有する(メタ)アクリレート単量体(b2−2)の少なくとも1種類(ただし、単量体(b1)を除く)を含む硬化性組成物(s2)の塗膜を形成し、硬化して、硬化被膜(B´´)を形成することを含み、さらに工程(2)の後に、下記工程(3)〜(5)を順次行うことを含む、樹脂積層体の製造方法にある。   The fifth gist of the present invention is that the step of forming the cured film (B) in the step (2) of the production method of the fourth gist comprises three or more molecules in the molecule on the surface of the cured film (A). At least one of a monomer (b1) having a (meth) acryloyloxy group, a urethane (meth) acrylate monomer (b2-1), and a (meth) acrylate monomer (b2-2) having an amino group Forming a coating film of the curable composition (s2) containing (except for the monomer (b1)) and curing to form a cured coating film (B ″); ) Is followed by the following steps (3) to (5) in order.

工程(3):樹脂フィルムの表面に、低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層から選ばれる少なくとも1つの機能を有する層からなる機能層(C)を形成する。 Step (3): a functional layer comprising a layer having at least one function selected from a low refractive index layer, a high refractive index layer, a hard coat layer, an antistatic layer, an antiglare layer and an antifouling layer on the surface of the resin film. (C) is formed.

工程(4):前記工程(4)で得られた硬化被膜(B´´)の表面に、前記工程(5)の機能層(C)を貼り合わせる。 Step (4): The functional layer (C) of the step (5) is bonded to the surface of the cured film (B ″) obtained in the step (4).

工程(5):前記樹脂フィルムを剥離し、樹脂基材の少なくとも一方の表面に、前記硬化被膜(A)、前記硬化被膜(B´´)、前記機能層(C)が順次積層された樹脂積層体を得る。 Step (5): A resin in which the resin film is peeled and the cured coating (A), the cured coating (B ″), and the functional layer (C) are sequentially laminated on at least one surface of a resin base material. A laminate is obtained.

本発明により、反射防止機能、帯電防止機能、防眩機能及び汚れ防止機能から選ばれる少なくとも一つの機能を有する層を備え、且つ、高い表面硬度、耐擦傷性、密着性及び耐クラック性を有する樹脂積層体を提供することができる。このような樹脂積層体は、液晶テレビ及び携帯電話等のディスプレイを保護するための前面板等に好適である。   According to the present invention, it has a layer having at least one function selected from an antireflection function, an antistatic function, an antiglare function, and an antifouling function, and has high surface hardness, scratch resistance, adhesion and crack resistance. A resin laminate can be provided. Such a resin laminate is suitable for a front plate or the like for protecting displays such as liquid crystal televisions and mobile phones.

以下、本発明を詳細に説明する。本発明において、「(メタ)アクリレート」及び「(メタ)アクリル酸」は、各々「アクリレート」及び「メタクリレート」から選ばれる少なくとも1種並びに「アクリル酸」及び「メタクリル酸」から選ばれる少なくとも1種のことをいう。   Hereinafter, the present invention will be described in detail. In the present invention, “(meth) acrylate” and “(meth) acrylic acid” are each at least one selected from “acrylate” and “methacrylate”, and at least one selected from “acrylic acid” and “methacrylic acid”. I mean.

また、「単量体」は未重合の単量体を意味し、「繰り返し単位」は単量体が重合することによって形成された該単量体に由来する単位のことをいう。繰り返し単位は、重合反応によって直接形成された単位であってもよく、ポリマーを処理することによって該単位の一部が別の構造に変換されたものであってもよい。   “Monomer” means an unpolymerized monomer, and “repeating unit” means a unit derived from the monomer formed by polymerization of the monomer. The repeating unit may be a unit directly formed by a polymerization reaction, or may be a part of the unit converted into another structure by treating the polymer.

また、「質量%」とは、特にことわりのない限り、全体量100質量%中に含まれる所定の成分の含有量を示す。   Moreover, "mass%" shows content of the predetermined | prescribed component contained in 100 mass% of whole quantity unless there is particular notice.

また、明細書中で「第1面」とは、2以上の層からなる積層体において、外側の表面のことをいう。
例えば、樹脂基材1の少なくとも一方の表面に硬化被膜2を備え、該硬化被膜2において樹脂基材1と接する面に対向する面のことを「硬化被膜2の第1面」という。
Further, in the specification, the “first surface” refers to an outer surface in a laminate composed of two or more layers.
For example, a surface that is provided with a cured coating 2 on at least one surface of the resin substrate 1 and faces the surface that contacts the resin substrate 1 in the cured coating 2 is referred to as a “first surface of the cured coating 2”.

<樹脂積層体>
本発明の樹脂積層体の第一の様態は、後述する樹脂基材の少なくとも一方の表面に後述する硬化被膜(A)を備え、硬化被膜(A)における樹脂基材と接する面と対向する面に硬化被膜(B)を順次備えたシート状の樹脂積層体である。
<Resin laminate>
The 1st aspect of the resin laminated body of this invention is equipped with the cured film (A) mentioned later on the at least one surface of the resin base material mentioned later, and the surface which opposes the surface which contacts the resin base material in a cured film (A). It is the sheet-like resin laminated body which provided the cured film (B) in order.

第一の様態の樹脂積層体において、前記硬化被膜(A)は、鉛筆硬度8H以上とすることが好ましい。鉛筆硬度の下限が、8H以上であれば、得られた樹脂積層体は高い表面硬度を有し、耐擦傷性が良好となる観点から好ましく、9H以上がより好ましい。一方、鉛筆硬度の上限は、特に制限されるものではない。硬化被膜(A)の鉛筆硬度の値は、後述するように、硬化被膜(A)を構成する(a1)成分及び(a2)成分の種類や含有量、硬化被膜(A)の膜厚等を適宜選択することにより、制御できる。   In the resin laminate of the first aspect, it is preferable that the cured film (A) has a pencil hardness of 8H or more. If the lower limit of the pencil hardness is 8H or more, the obtained resin laminate is preferable from the viewpoint of high surface hardness and good scratch resistance, and more preferably 9H or more. On the other hand, the upper limit of pencil hardness is not particularly limited. As will be described later, the value of the pencil hardness of the cured film (A) includes the types and contents of the (a1) and (a2) components constituting the cured film (A), the film thickness of the cured film (A), and the like. It can control by selecting suitably.

また、第一の様態の樹脂積層体において、記硬化被膜(B)は、後述するウレタン(メタ)アクリレート由来の繰り返し単位(b2−1)及び後述するアミノ基を有する(メタ)アクリレート由来の繰り返し単位(b2−2)の少なくとも1種類を含むことができる。   In the resin laminate of the first embodiment, the cured coating (B) is a repeating unit derived from a urethane (meth) acrylate described later (b2-1) and a repeating unit derived from a (meth) acrylate having an amino group described later. At least one type of unit (b2-2) can be included.

前記硬化被膜(B)には、低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層から選ばれる1つの機能を有する層からなる機能層を用いることができる。具体的な低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層としては、特に制限されるものではなく、公知の樹脂組成物からなる機能層を用いることができる。   For the cured coating (B), a functional layer comprising a layer having one function selected from a low refractive index layer, a high refractive index layer, a hard coat layer, an antistatic layer, an antiglare layer and an antifouling layer is used. Can do. The specific low refractive index layer, high refractive index layer, hard coat layer, antistatic layer, antiglare layer and antifouling layer are not particularly limited, and a functional layer made of a known resin composition is used. be able to.

これにより、第一の様態の樹脂積層体は、反射防止機能、帯電防止機能、防眩機能及び汚れ防止機能から選ばれる少なくとも一つの機能を備えるとともに、樹脂積層体の表面の鉛筆硬度が8H以上となるので、高い表面硬度、耐擦傷性を有することができる。   Accordingly, the resin laminate of the first aspect has at least one function selected from an antireflection function, an antistatic function, an antiglare function, and a stain prevention function, and the pencil hardness of the surface of the resin laminate is 8H or more. Therefore, it can have high surface hardness and scratch resistance.

さらに、第一の様態の樹脂積層体においては、、ISO 2409:1992に準拠したクロスカット剥離試験による硬化被膜(B)の残存率は、樹脂積層体の耐擦傷性や耐クラック性が良好となる観点から80%以上であることが好ましく、90%以上であることがより好ましく、100%であることがさらに好ましい。ここでいう硬化被膜(B)の残存率とは、クロスカット剥離試験後に剥離せずに樹脂シート上に残存する硬化被膜(B)の残存率のことをいう。前記残存率の値は、後述するように、硬化被膜(A)を構成する(a1)成分及び(a2)成分の種類や含有量、硬化被膜(A)の膜厚、並びに硬化被膜(B)を構成する(b1)成分、(b2)成分の種類や含有量、硬化被膜(B)の膜厚を適宜選択することにより、制御することができる。   Furthermore, in the resin laminate of the first aspect, the residual ratio of the cured film (B) by the cross-cut peel test in accordance with ISO 2409: 1992 indicates that the resin laminate has good scratch resistance and crack resistance. From this viewpoint, it is preferably 80% or more, more preferably 90% or more, and further preferably 100%. The residual rate of the cured coating (B) here refers to the residual rate of the cured coating (B) that remains on the resin sheet without peeling after the cross-cut peeling test. As will be described later, the value of the residual ratio is the type and content of the (a1) component and (a2) component constituting the cured coating (A), the thickness of the cured coating (A), and the cured coating (B). It is possible to control by appropriately selecting the type and content of the component (b1), the component (b2), and the thickness of the cured coating (B).

本発明の樹脂積層体の第二の様態は、第一の様態の樹脂積層体の硬化被膜(B)の表面に後述する機能層(C)が積層されたシート状の樹脂積層体である。   The 2nd aspect of the resin laminated body of this invention is a sheet-like resin laminated body by which the functional layer (C) mentioned later was laminated | stacked on the surface of the cured film (B) of the resin laminated body of a 1st aspect.

第二の様態の樹脂積層体において、前記硬化被膜(A)の鉛筆硬度は8H以上とすることが、第一の様態の樹脂積層体で述べたのと同じ理由で好ましい。   In the resin laminate of the second embodiment, the pencil hardness of the cured film (A) is preferably 8H or more for the same reason as described in the resin laminate of the first embodiment.

また、第二の様態の樹脂積層体において、記硬化被膜(B)は、低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層から選ばれる1つの機能を有する層からなる機能層を用いることができる。具体的な低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層としては、特に制限されるものではなく、公知の樹脂組成物からなる機能層を用いることができる。   In the second aspect of the resin laminate, the cured coating (B) is one selected from a low refractive index layer, a high refractive index layer, a hard coat layer, an antistatic layer, an antiglare layer and an antifouling layer. A functional layer composed of a layer having a function can be used. The specific low refractive index layer, high refractive index layer, hard coat layer, antistatic layer, antiglare layer and antifouling layer are not particularly limited, and a functional layer made of a known resin composition is used. be able to.

これにより、第二の様態の樹脂積層体は、反射防止機能、帯電防止機能、防眩機能及び汚れ防止機能から選ばれる少なくとも一つの機能を備えるとともに、樹脂積層体の表面の鉛筆硬度が8H以上とすることができるので、高い表面硬度、耐擦傷性を有することができる。硬化被膜(A)の鉛筆硬度の値は、上述した方法により制御することができる。   Accordingly, the resin laminate of the second aspect has at least one function selected from an antireflection function, an antistatic function, an antiglare function, and a stain prevention function, and the pencil hardness of the surface of the resin laminate is 8H or more. Therefore, it can have high surface hardness and scratch resistance. The pencil hardness value of the cured coating (A) can be controlled by the method described above.

第二の様態の樹脂積層体においては、、ISO 2409:1992に準拠したクロスカット剥離試験による前記硬化被膜(B)および前記機能層(C)の残存率は、樹脂積層体の耐擦傷性や耐クラック性が良好となる観点から80%以上であることが好ましく、90%以上であることがより好ましく、100%であることがさらに好ましい。ここでいう前記硬化被膜(B)および前記機能層(C)の残存率とは、クロスカット剥離試験後に剥離せずに樹脂積層体上に残存する前記硬化被膜(B)および前記機能層(C)の残存率のことをいう。前記残存率の値は、後述するように、硬化被膜(A)を構成する(a1)成分及び(a2)成分の種類や含有量、硬化被膜(A)の膜厚、並びに硬化被膜(B)を構成する(b1)成分、(b2)成分の種類や含有量、硬化被膜(B)の膜厚を適宜選択することにより、制御することができる。   In the resin laminate of the second aspect, the residual ratio of the cured film (B) and the functional layer (C) by the cross-cut peel test in accordance with ISO 2409: 1992 is the scratch resistance of the resin laminate. From the viewpoint of good crack resistance, it is preferably 80% or more, more preferably 90% or more, and even more preferably 100%. The residual ratio of the cured film (B) and the functional layer (C) as used herein refers to the cured film (B) and the functional layer (C) remaining on the resin laminate without being peeled after the cross-cut peel test. ). As will be described later, the value of the residual ratio is the type and content of the (a1) component and (a2) component constituting the cured coating (A), the thickness of the cured coating (A), and the cured coating (B). It is possible to control by appropriately selecting the type and content of the component (b1), the component (b2), and the thickness of the cured coating (B).

本発明の樹脂積層体の第三の様態は、後述する樹脂基材の少なくとも一方の表面に、下記の硬化被膜(A)を備え、前記硬化被膜(A)における樹脂基材と接する面と対向する面に下記の硬化被膜(B)を備え、前記硬化被膜(B)における硬化被膜(A)と接する面と対向する面に下記の機能層(C)が順次積層されたシート状の樹脂積層体である。   The third aspect of the resin laminate of the present invention is provided with the following cured coating (A) on at least one surface of a resin substrate described later, and opposed to the surface in contact with the resin substrate in the cured coating (A). A sheet-like resin laminate comprising the following cured coating (B) on the surface to be coated, and the following functional layers (C) sequentially laminated on the surface facing the cured coating (A) in the cured coating (B) Is the body.

第三の様態の樹脂積層体において、前記硬化被膜(A)は、分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(a1)と、分子中に2個以下の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(a2)を含むことができる。   In the resin laminate according to the third aspect, the cured coating (A) has two or more repeating units (a1) derived from a monomer having three or more (meth) acryloyloxy groups in the molecule and two in the molecule. The repeating unit (a2) derived from a monomer having the following (meth) acryloyloxy group can be included.

前記硬化被膜(A)の鉛筆硬度は8H以上とすることが、第一の様態の樹脂積層体で述べたのと同じ理由により好ましい。前記硬化被膜(A)の鉛筆硬度は、前記硬化被膜(A)に含まれる前記繰り返し単位(a1)及び前記繰り返し単位(a2)の含有量を適宜調整することにより制御できる。   The pencil hardness of the cured coating (A) is preferably 8H or more for the same reason as described in the resin laminate of the first aspect. The pencil hardness of the cured coating (A) can be controlled by appropriately adjusting the contents of the repeating unit (a1) and the repeating unit (a2) contained in the cured coating (A).

また、第三の様態の樹脂積層体において、硬化被膜(B)は、ウレタン(メタ)アクリレート単位(b2−1)及びアミノ基を有する(メタ)アクリレート単位(b2−2)の少なくとも1種類を含むことができる。前記の単位(b2−1)及び前記の単位(b2−2)を含むことにより、樹脂積層体において、硬化被膜(B)と硬化被膜(A)との密着性、樹脂積層体の耐擦傷性は良好となる。   Moreover, in the resin laminated body of the 3rd aspect, a cured film (B) contains at least 1 sort (s) of the urethane (meth) acrylate unit (b2-1) and the (meth) acrylate unit (b2-2) which has an amino group. Can be included. By including the unit (b2-1) and the unit (b2-2), in the resin laminate, adhesion between the cured coating (B) and the cured coating (A), and scratch resistance of the resin laminate. Is good.

これにより、第三の様態の樹脂積層体は、樹脂積層体の表面の鉛筆硬度を8H以上とすることができるので、高い表面硬度、耐擦傷性を有することができる。硬化被膜(A)の鉛筆硬度の値は、後述するように、硬化被膜(A)及び硬化被膜(B)の組成や膜厚等を適宜選択することにより、制御できる。   Thereby, since the resin laminated body of the 3rd aspect can make the pencil hardness of the surface of a resin laminated body 8H or more, it can have high surface hardness and scratch resistance. As will be described later, the value of the pencil hardness of the cured coating (A) can be controlled by appropriately selecting the composition and film thickness of the cured coating (A) and the cured coating (B).

また、第三の様態の樹脂積層体は、前記硬化被膜(B)の表面に、上述した機能層(C)を積層することもできる。   Moreover, the resin laminated body of a 3rd aspect can also laminate | stack the functional layer (C) mentioned above on the surface of the said cured film (B).

<樹脂基材>
本発明の樹脂積層体に用いる樹脂基材としては、例えば、ポリオレフィン樹脂、(メタ)アクリル樹脂、エポキシ樹脂、ポリイミド樹脂、フェノール樹脂、ポリエステル樹脂及びポリカーボネート樹脂が挙げられる。樹脂基材は、上記の樹脂が複数積層されていてもよい。
<Resin substrate>
Examples of the resin base material used in the resin laminate of the present invention include polyolefin resin, (meth) acrylic resin, epoxy resin, polyimide resin, phenol resin, polyester resin, and polycarbonate resin. A plurality of the above resins may be laminated on the resin base material.

樹脂基材としては、該樹脂基材を構成する樹脂の総重量を100質量%として、(メタ)アクリル樹脂を90〜100質量%含有することが、樹脂積層体の透明性が良好となる観点から好ましい。   As the resin base material, the total weight of the resin constituting the resin base material is 100% by mass, and 90 to 100% by mass of (meth) acrylic resin is contained, whereby the transparency of the resin laminate is improved. To preferred.

樹脂基材を構成する(メタ)アクリル樹脂は、メチルメタクリレート単位を主成分とする重合体が好ましい。上述したメチルメタクリレート単位を主成分とする重合体としては、前記(メタ)アクリル樹脂の総重量を100質量%として、メチルメタクリレート由来の繰り返し単位を50〜100質量%を含有する重合体が好ましく、80〜100質量%を含有する重合体がさらに好ましく、100質量%からなる重合体がさらに好ましい。   The (meth) acrylic resin constituting the resin base material is preferably a polymer having a methyl methacrylate unit as a main component. As the polymer having the methyl methacrylate unit as a main component, a polymer containing 50 to 100% by mass of repeating units derived from methyl methacrylate is preferable, with the total weight of the (meth) acrylic resin being 100% by mass, A polymer containing 80 to 100% by mass is more preferable, and a polymer composed of 100% by mass is more preferable.

前記(メタ)アクリル樹脂がメチルメタクリレート単位を主成分とする重合体の場合、該重合体を構成するメチルメタクリレートと共重合可能な単量体(以下、「その他の共重合可能な単量体」と略する。)としては、例えば以下が挙げられる。   When the (meth) acrylic resin is a polymer having a methyl methacrylate unit as a main component, a monomer copolymerizable with methyl methacrylate constituting the polymer (hereinafter referred to as “other copolymerizable monomer”). For example, the following may be mentioned.

1)メチルアクリレート、エチル(メタ)アクリレート、イソプロピル(メタ)アクリレート、n−ブチル(メタ)アクリレート、iso−ブチル(メタ)アクリレート、tert−ブチル(メタ)アクリレート、2−エチルヘキシル(メタ)アクリレート、フェニルメタクリレート、ベンジルメタクリレート等の(メタ)アクリル酸エステル; 1) Methyl acrylate, ethyl (meth) acrylate, isopropyl (meth) acrylate, n-butyl (meth) acrylate, iso-butyl (meth) acrylate, tert-butyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, phenyl (Meth) acrylic acid esters such as methacrylate and benzyl methacrylate;

2)(メタ)アクリル酸、マレイン酸、イタコン酸等の不飽和カルボン酸; 無水マレイン酸、無水イタコン酸等の不飽和カルボン酸無水物; 2) Unsaturated carboxylic acids such as (meth) acrylic acid, maleic acid and itaconic acid; unsaturated carboxylic acid anhydrides such as maleic anhydride and itaconic anhydride;

3)N−フェニルマレイミド、N−シクロヘキシルマレイミド等のマレイミド; 3) Maleimides such as N-phenylmaleimide and N-cyclohexylmaleimide;

4)2−ヒドロキシエチル(メタ)アクリレート、2−ヒドロキシプロピル(メタ)アクリレート等のヒドロキシ基含有ビニル単量体; 4) Hydroxy group-containing vinyl monomers such as 2-hydroxyethyl (meth) acrylate and 2-hydroxypropyl (meth) acrylate;

5)酢酸ビニル、安息香酸ビニル等のビニルエステル;塩化ビニル、塩化ビニリデン及びそれらの誘導体;(メタ)アクリルアミド、(メタ)アクリロニトリル等の窒素含有ビニル単量体;グリシジル(メタ)アクリレート等のエポキシ基含有単量体; 5) Vinyl esters such as vinyl acetate and vinyl benzoate; vinyl chloride, vinylidene chloride and derivatives thereof; nitrogen-containing vinyl monomers such as (meth) acrylamide and (meth) acrylonitrile; epoxy groups such as glycidyl (meth) acrylate Containing monomer;

6)スチレン、α−メチルスチレン等の芳香族ビニル単量体。 6) Aromatic vinyl monomers such as styrene and α-methylstyrene.

これらの中で、樹脂基材の吸水率を低下させる点で、n−ブチルアクリレート、tert−ブチルメタクリレート及びイソボニル(メタ)アククリレートが好ましい。   Among these, n-butyl acrylate, tert-butyl methacrylate and isobornyl (meth) acrylate are preferable in terms of reducing the water absorption rate of the resin base material.

また、その他の共重合可能な単量体としては、上記の単量体以外に、例えば以下が挙げられる。   Examples of other copolymerizable monomers include the following in addition to the above monomers.

7)エチレングリコールジ(メタ) アクリレート、1,2−プロピレングリコールジ(メタ)アクリレート、1,3−ブチレングリコールジ(メタ)アクリレート、1,6−ヘキサンジオールジ(メタ)アクリレート等のアルカンジオールジ(メタ)アクリレート; 7) Alkanediol di (meth) acrylate such as ethylene glycol di (meth) acrylate, 1,2-propylene glycol di (meth) acrylate, 1,3-butylene glycol di (meth) acrylate, 1,6-hexanediol di (meth) acrylate (Meth) acrylate;

8)ジエチレングリコールジ(メタ)アクリレート、ジプロピレングリコールジ(メタ)アクリレート、トリエチレングリコール(メタ)アクリレート、テトラエチレングリコールジ(メタ)アクリレート、ポリエチレングリコールジ(メタ)アクリレート、ネオペンチルグリコールジ(メタ)アクリレート等のポリオキシアルキレングリコールジ(メタ)アクリレート; 8) Diethylene glycol di (meth) acrylate, dipropylene glycol di (meth) acrylate, triethylene glycol (meth) acrylate, tetraethylene glycol di (meth) acrylate, polyethylene glycol di (meth) acrylate, neopentyl glycol di (meth) Polyoxyalkylene glycol di (meth) acrylates such as acrylates;

9)ジビニルベンゼン等の分子中に2個以上のエチレン性不飽和結合を有するビニル単量体; 9) A vinyl monomer having two or more ethylenically unsaturated bonds in a molecule such as divinylbenzene;

10)エチレン性不飽和ポリカルボン酸を含む少なくとも1 種の多価カルボン酸と少なくとも1種のジオールから得られる不飽和ポリエステルプレポリマー; 10) an unsaturated polyester prepolymer obtained from at least one polycarboxylic acid containing ethylenically unsaturated polycarboxylic acid and at least one diol;

11)及びエポキシ基の末端をアクリル変性することにより得られるビニルエステルプレポリマー
これらの中では、樹脂積層体の耐熱性を向上させる点で、ネオペンチルグリコールジメタクリレートが好ましい。
11) and a vinyl ester prepolymer obtained by modifying the terminal of the epoxy group with acrylic. Among these, neopentyl glycol dimethacrylate is preferred in terms of improving the heat resistance of the resin laminate.

樹脂基材にメチルメタクリレート単位を主成分とする重合体は、樹脂基材原料を重合することにより得ることができる。   A polymer having a methyl methacrylate unit as a main component on the resin base material can be obtained by polymerizing the resin base material.

樹脂基材原料としては、例えば、下記の(a)〜(c)が挙げられるが、これらに限定されるものではない。
(a)メチルメタクリレート50質量%以上100質量%とその他の共重合可能な単量体0質量%以上50質量%を含有するラジカル重合性単量体混合物が挙げられる。
(b)前記ラジカル重合性単量体混合物の一部を重合させた、部分重合体と未重合のラジカル重合性単量体との混合物(以下、「シラップ1」と称する。)
(c)前記ラジカル重合性単量体混合物に、このラジカル重合性単量体の混合物と同一又は異なる組成の単量体原料から得られる(メタ)アクリル樹脂を溶解させた、(メタ)アクリル樹脂とラジカル重合性単量体との混合物(以下、「シラップ2」と称する。)。
Examples of the resin base material include (a) to (c) below, but are not limited thereto.
(A) A radical polymerizable monomer mixture containing 50% by mass or more and 100% by mass of methyl methacrylate and 0% by mass or more and 50% by mass of another copolymerizable monomer may be mentioned.
(B) A mixture of a partial polymer and an unpolymerized radical polymerizable monomer obtained by polymerizing a part of the radical polymerizable monomer mixture (hereinafter referred to as “syrup 1”).
(C) A (meth) acrylic resin obtained by dissolving a (meth) acrylic resin obtained from a monomer raw material having the same or different composition as the radical polymerizable monomer mixture in the radical polymerizable monomer mixture. And a radically polymerizable monomer (hereinafter referred to as “syrup 2”).

樹脂基材原料には、必要に応じて、着色剤、離型剤、酸化防止剤、安定剤、難燃剤、耐衝撃改質剤、光安定剤、紫外線吸収剤、重合禁止剤、連鎖移動剤等の各種添加剤を添加することができる。   Resin base materials include colorants, mold release agents, antioxidants, stabilizers, flame retardants, impact modifiers, light stabilizers, UV absorbers, polymerization inhibitors, chain transfer agents as necessary. Various additives such as can be added.

前記樹脂基材原料には、重合開始剤を添加することができる。重合開始剤としては、公知の有機過酸化物やアゾ系化合物、公知の有機過酸化物にN,N−ジメチルアニリン、N,N−ジメチル−p−トルイジン等のアミン類を組み合わせたレドックス重合開始剤が挙げられる。重合開始剤の添加量は、樹脂基材原料中のラジカル重合性単量体100質量部に対し、0.005質量部以上5.0質量部以下が好ましい。   A polymerization initiator can be added to the resin base material. As a polymerization initiator, a known organic peroxide or an azo compound, a redox polymerization in which a known organic peroxide is combined with an amine such as N, N-dimethylaniline or N, N-dimethyl-p-toluidine Agents. The addition amount of the polymerization initiator is preferably 0.005 parts by mass or more and 5.0 parts by mass or less with respect to 100 parts by mass of the radical polymerizable monomer in the resin base material.

樹脂基材原料の重合方法としては、例えば、公知の塊状重合法、溶液重合法、乳化重合法及び懸濁重合法を用いることができる。その中でも(メタ)アクリル樹脂組成物の製造コスト、溶剤使用による環境負荷、(メタ)アクリル樹脂成形体の生産性及び透明性に優れる観点から、塊状重合法が好ましい。   As a polymerization method of the resin base material, for example, a known bulk polymerization method, solution polymerization method, emulsion polymerization method and suspension polymerization method can be used. Among these, the bulk polymerization method is preferable from the viewpoint of excellent production cost of the (meth) acrylic resin composition, environmental load due to the use of a solvent, productivity of the (meth) acrylic resin molded product, and transparency.

樹脂基材の厚さは、特に制限されるものではないが、0.1mm以上10mm以下とすることができる。0.3mm以上3.0mm以下がより好ましい。なお、本願において樹脂基材の厚みは、ノギスを使用して上面から底面までの距離を任意の5箇所測定した平均値をいう。   The thickness of the resin base material is not particularly limited, but can be 0.1 mm or more and 10 mm or less. 0.3 mm or more and 3.0 mm or less are more preferable. In addition, in this application, the thickness of a resin base material says the average value which measured the distance from an upper surface to a bottom face using arbitrary calipers five places.

<硬化被膜(A)>
本発明の一つの側面として、硬化被膜(A)は、本発明の樹脂積層体を構成する構成要素の1つで、樹脂基材の第1面に形成されているものである。硬化被膜(A)を構成する樹脂組成物は、分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(a1)、分子中に2個以下の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(a2)を含む。
<Hardened film (A)>
As one aspect of the present invention, the cured coating (A) is one of the components constituting the resin laminate of the present invention, and is formed on the first surface of the resin base material. The resin composition constituting the cured coating (A) is composed of a repeating unit (a1) derived from a monomer having 3 or more (meth) acryloyloxy groups in the molecule and 2 or less (meth) acryloyl in the molecule. It contains a repeating unit (a2) derived from a monomer having an oxy group.

なお、本明細書においては、前記(a1)由来の繰り返し単位を構成する単量体のことを「(a1)成分」といい、前記(a2)由来の繰り返し単位を構成する単量体を「(a2)成分」という。   In the present specification, the monomer constituting the repeating unit derived from (a1) is referred to as “component (a1)”, and the monomer constituting the repeating unit derived from (a2) is represented by “ (A2) component ".

硬化被膜(A)の膜厚は、特に制限されるものではないが、17μm以上40μm以下とすることができる。膜厚の下限は、硬化被膜の耐擦傷性及び表面硬度が良好となる観点から17μm以上が好ましく、20μm以上がより好ましく、25μm以上がさらに好ましい。また、膜厚の上限は、樹脂製品の切断時の割れを抑制でき、樹脂製品の取り扱い時に硬化被膜にクラックが発生するのを抑制でき、加工性が良好となる観点から40μm以下が好ましく、35μmがより好ましい。即ち、硬化被膜の膜厚は、25μm以上35μm以下がより好ましい。ここでいう硬化被膜(A)の膜厚とは、樹脂積層体における硬化被膜(A)の膜厚のことをいう。   The film thickness of the cured coating (A) is not particularly limited, but can be 17 μm or more and 40 μm or less. The lower limit of the film thickness is preferably 17 μm or more, more preferably 20 μm or more, and even more preferably 25 μm or more from the viewpoint of good scratch resistance and surface hardness of the cured film. In addition, the upper limit of the film thickness is preferably 40 μm or less from the viewpoint of being able to suppress cracking during cutting of the resin product, suppressing cracks from occurring in the cured film during handling of the resin product, and improving workability. Is more preferable. That is, the film thickness of the cured coating is more preferably 25 μm or more and 35 μm or less. The film thickness of a cured film (A) here means the film thickness of the cured film (A) in the resin laminate.

本発明において、硬化被膜(A)は、樹脂積層体の表面硬度及び耐擦傷性の点で、鉛筆硬度8H以上の硬度の表面を有するものであることが好ましい。尚、本発明において、鉛筆硬度はJISO 2409:1992に準拠して得られた値である。   In the present invention, the cured coating (A) preferably has a surface with a pencil hardness of 8H or more from the viewpoint of the surface hardness and scratch resistance of the resin laminate. In the present invention, the pencil hardness is a value obtained according to JISO 2409: 1992.

<(a1)成分>
本発明において、(a1)成分は、分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位を構成する単量体である。
<(A1) component>
In the present invention, the component (a1) is a monomer constituting a repeating unit derived from a monomer having three or more (meth) acryloyloxy groups in the molecule.

硬化被膜(A)が(a1)成分を含むことにより、樹脂積層体の耐擦傷性及び表面硬度を向上すること、硬化被膜(A)の耐クラック性を向上すること、樹脂基材に対する硬化被膜(A)の密着性を向上することができる。   When the cured coating (A) contains the component (a1), the scratch resistance and surface hardness of the resin laminate are improved, the crack resistance of the cured coating (A) is improved, and the cured coating on the resin substrate. The adhesion of (A) can be improved.

(a1)成分としては、(メタ)アクリロイルオキシ基を有する単量体が挙げられ、例えば、(メタ)アクリロイルオキシ基を3個以上、20個以下有する単量体が挙げられる。   (A1) As a component, the monomer which has a (meth) acryloyloxy group is mentioned, For example, the monomer which has 3 or more and 20 or less (meth) acryloyloxy groups is mentioned.

(a1)成分の具体例としては、各(メタ)アクリロイルオキシ基に結合する残基が炭化水素基又はその誘導体である単量体が挙げられ、その分子内にはエーテル結合、チオエーテル結合、エステル結合、アミド結合、ウレタン結合等の結合を含むことができる。   Specific examples of the component (a1) include monomers in which the residue bonded to each (meth) acryloyloxy group is a hydrocarbon group or a derivative thereof, and in the molecule, an ether bond, a thioether bond, an ester A bond such as a bond, an amide bond, and a urethane bond can be included.

(a1)成分の具体例としては、1モルの多価アルコールと、3モル以上の(メタ)アクリル酸又はその誘導体とから得られるエステル化物及び多価アルコールと、多価カルボン酸又はその無水物と、(メタ)アクリル酸又はその誘導体とから得られる線状のエステル化物が挙げられる。   Specific examples of the component (a1) include an esterified product and a polyhydric alcohol obtained from 1 mol of a polyhydric alcohol and 3 mol or more of (meth) acrylic acid or a derivative thereof, and a polyvalent carboxylic acid or an anhydride thereof. And a linear esterified product obtained from (meth) acrylic acid or a derivative thereof.

尚、ここでいう「多価アルコール」とは、分子中に水酸基を2個以上有するアルコールのことをいう。「多価カルボン酸」とは、分子中にカルボキシル基を2個以上有するカルボン酸のことをいう。「(メタ)アクリル酸の誘導体」とは、(メタ)アクリル酸の水素原子が、他の官能基に置換された化合物のことをいう。「線状」とは、直鎖状及び分岐鎖状のことをいう。   As used herein, “polyhydric alcohol” refers to an alcohol having two or more hydroxyl groups in the molecule. “Polyvalent carboxylic acid” refers to a carboxylic acid having two or more carboxyl groups in the molecule. The “derivative of (meth) acrylic acid” refers to a compound in which a hydrogen atom of (meth) acrylic acid is substituted with another functional group. “Linear” means linear and branched.

1モルの多価アルコールと、3モル以上の(メタ)アクリル酸又はその誘導体とから得られるエステル化物の例としては、トリメチロールプロパントリ(メタ)アクリレート、トリメチロールエタントリ(メタ)アクリレート、エチレンオキシド付加物トリメチロールプロパントリ(メタ)アクリレート、プロピレンオキシド付加物トリメチロールプロパントリ(メタ)アクリレート、ジトリメチロールプロパンテトラ(メタ)アクリレート、ペンタグリセロールトリ(メタ)アクリレート、ペンタエリスリトールトリ(メタ)アクリレート、ペンタエリスリトールテトラ(メタ)アクリレート、グリセリントリ(メタ)アクリレート、ジペンタエリスリトールトリ(メタ)アクリレート、ジペンタエリスリトールテトラ(メタ)アクリレート、トリペンタエリスリトールテトラ(メタ) アクリレート、エチレンオキシド付加物ペンタエリスリトールテトラ(メタ)アクリレート、ジペンタエリスリトールペンタ(メタ)アクリレート、ジペンタエリスリトールヘキサ(メタ)アクリレート、カプロラクトン付加物ジペンタエリスリトールペンタ(メタ)アクリレート及びカプロラクトン付加物ジペンタエリスリトールヘキサ(メタ)アクリレートが挙げられる。   Examples of esterified products obtained from 1 mol of polyhydric alcohol and 3 mol or more of (meth) acrylic acid or derivatives thereof include trimethylolpropane tri (meth) acrylate, trimethylolethane tri (meth) acrylate, ethylene oxide Adduct trimethylolpropane tri (meth) acrylate, propylene oxide adduct trimethylolpropane tri (meth) acrylate, ditrimethylolpropane tetra (meth) acrylate, pentaglycerol tri (meth) acrylate, pentaerythritol tri (meth) acrylate, penta Erythritol tetra (meth) acrylate, glycerin tri (meth) acrylate, dipentaerythritol tri (meth) acrylate, dipentaerythritol tetra (meth) acrylate , Tripentaerythritol tetra (meth) acrylate, ethylene oxide adduct pentaerythritol tetra (meth) acrylate, dipentaerythritol penta (meth) acrylate, dipentaerythritol hexa (meth) acrylate, caprolactone adduct dipentaerythritol penta (meth) acrylate And caprolactone adduct dipentaerythritol hexa (meth) acrylate.

多価アルコールと、多価カルボン酸又はその無水物と、(メタ)アクリル酸又はその誘導体とから得られる線状のエステル化物において、多価アルコールと、多価カルボン酸又はその無水物と、(メタ)アクリル酸の好ましい組み合わせ例としては、マロン酸/トリメチロールエタン/(メタ)アクリル酸、マロン酸/トリメチロールプロパン/(メタ)アクリル酸、マロン酸/グリセリン/(メタ)アクリル酸、マロン酸/ペンタエリスリトール/(メタ)アクリル酸、コハク酸/トリメチロールエタン/(メタ)アクリル酸、アジピン酸/トリメチロールエタン/(メタ)アクリル酸、グルタル酸/トリメチロールエタン/(メタ)アクリル酸、セバシン酸/トリメチロールエタン/(メタ)アクリル酸、、フマル酸/トリメチロールエタン/(メタ)アクリル酸、イタコン酸/トリメチロールエタン/(メタ)アクリル酸、無水マレイン酸/トリメチロールプロパン/(メタ)アクリル酸等が挙げられる。これらは、1種又は2種以上を組み合わせて使用してもよい。   In a linear esterified product obtained from a polyhydric alcohol, a polyhydric carboxylic acid or an anhydride thereof, and (meth) acrylic acid or a derivative thereof, the polyhydric alcohol, the polyhydric carboxylic acid or an anhydride thereof, Preferred examples of combinations of (meth) acrylic acid include malonic acid / trimethylolethane / (meth) acrylic acid, malonic acid / trimethylolpropane / (meth) acrylic acid, malonic acid / glycerin / (meth) acrylic acid, malonic acid / Pentaerythritol / (meth) acrylic acid, succinic acid / trimethylolethane / (meth) acrylic acid, adipic acid / trimethylolethane / (meth) acrylic acid, glutaric acid / trimethylolethane / (meth) acrylic acid, sebacine Acid / trimethylolethane / (meth) acrylic acid, fumaric acid / trimethylolethane Emissions / (meth) acrylic acid, itaconic acid / trimethylolethane / (meth) acrylic acid, maleic acid / trimethylolpropane / (meth) acrylic anhydride. These may be used alone or in combination of two or more.

(a1)成分としては、上記の中から1種の単量体を単独で又は2種以上の単量体を組み合わせて使用することができる。   As the component (a1), one type of monomer can be used alone, or two or more types of monomers can be used in combination.

(a1)成分としては、硬化被膜(A)の耐擦傷性及び表面硬度の点で、ペンタエリスリトールトリ(メタ)アクリレート、ペンタエリスリトールテトラ(メタ)アクリレート、ジペンタエリスリトールペンタ(メタ)アクリレート及びジペンタエリスリトールヘキサ(メタ)アクリレートがより好ましい。   As the component (a1), pentaerythritol tri (meth) acrylate, pentaerythritol tetra (meth) acrylate, dipentaerythritol penta (meth) acrylate and dipenta are used in terms of scratch resistance and surface hardness of the cured coating (A). Erythritol hexa (meth) acrylate is more preferred.

(a1)成分の含有量は特に制限されるものではないが、(a1)成分及び後述する(a2)成分を含む硬化性組成物の総重量100質量%に対して、55質量%以上90質量%以下とすることができる。(a1)成分の含有量の下限は、硬化被膜(A)の耐擦傷性及び表面硬度が良好となる観点から50質量%以上が好ましく、60質量%以上がより好ましく、65質量%以上がさらに好ましい。(a1)成分の含有量の上限は、(a1)成分及び後述する(a2)成分を含む硬化性組成物を硬化させる際の硬化収縮率が低下し、硬化被膜(A)の耐クラック性が良好となり、樹脂基材に対する硬化被膜(A)の密着性が良好となる観点から、が90質量%以下が好ましく、85質量%以下がより好ましく、75質量%以下がさらに好ましい。   The content of the component (a1) is not particularly limited, but 55% by mass or more and 90% by mass with respect to 100% by mass of the total weight of the curable composition containing the component (a1) and the component (a2) described later. % Or less. The lower limit of the content of the component (a1) is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 65% by mass or more from the viewpoint of improving the scratch resistance and surface hardness of the cured coating (A). preferable. The upper limit of the content of the component (a1) is that the curing shrinkage rate when the curable composition containing the component (a1) and the component (a2) described later is cured is reduced, and the crack resistance of the cured film (A) is reduced. From the viewpoint of improving the adhesion of the cured film (A) to the resin base material, is preferably 90% by mass or less, more preferably 85% by mass or less, and further preferably 75% by mass or less.

<(a2)成分>
本発明において、(a2)成分は、分子中に2個以下の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位を構成する単量体である。
<(A2) component>
In the present invention, the component (a2) is a monomer constituting a repeating unit derived from a monomer having 2 or less (meth) acryloyloxy groups in the molecule.

硬化被膜(A)が(a2)成分を含むことにより、硬化被膜(A)と樹脂基材の密着性が向上すること、硬化被膜(A)の耐クラック性が向上すること及び硬化被膜(A)を積層したときの樹脂積層体の反りを抑制することができる。   When the cured coating (A) contains the component (a2), the adhesion between the cured coating (A) and the resin substrate is improved, the crack resistance of the cured coating (A) is improved, and the cured coating (A ) Can be prevented from warping.

(a2)成分としては、例えば、以下のものが挙げられる。   Examples of the component (a2) include the following.

分子内に2個の(メタ)アクリロイル基を有する(メタ)アクリレート単量体として、例えば、エチレングリコールジ(メタ)アクリレート、ジシクロペンテニルジ(メタ)アクリレート、トリエチレングリコールジ(メタ)アクリレート、テトラエチレングリコールジ(メタ)アクリレート、ポリエチレングリコールジ(メタ)アクリレート、トリメチロールプロパンジ(メタ)アクリレート、エチレンオキシド変性トリメチロールプロパンジ(メタ)アクリレート、トリプロピレングリコールジ(メタ)アクリレート、ネオペンチルグリコールジ(メタ)アクリレート、1,4−ブタンジオールジ(メタ)アクリレート、1,6−ヘキサンジオールジ(メタ)アクリレート、ポリエステルジ(メタ)アクリレート、ポリエチレングリコールジ(メタ)アクリレート、トリシクロデカンジメチロールジ(メタ)アクリレート、ヒドロキシピバリン酸ネオペンチルグリコールジ(メタ)アクリレート、ビスフェノールAポリエトキシジ(メタ)アクリレート、1,10−デカンジオールジ(メタ)アクリレート及びヒドロキシピバリン酸ネオペンチルグリコールジ(メタ)アクリレートが挙げられる。   As a (meth) acrylate monomer having two (meth) acryloyl groups in the molecule, for example, ethylene glycol di (meth) acrylate, dicyclopentenyl di (meth) acrylate, triethylene glycol di (meth) acrylate, Tetraethylene glycol di (meth) acrylate, polyethylene glycol di (meth) acrylate, trimethylolpropane di (meth) acrylate, ethylene oxide modified trimethylolpropane di (meth) acrylate, tripropylene glycol di (meth) acrylate, neopentyl glycol di (Meth) acrylate, 1,4-butanediol di (meth) acrylate, 1,6-hexanediol di (meth) acrylate, polyester di (meth) acrylate, polyethylene glycol Di (meth) acrylate, tricyclodecane dimethylol di (meth) acrylate, hydroxypivalate neopentyl glycol di (meth) acrylate, bisphenol A polyethoxydi (meth) acrylate, 1,10-decandiol di (meth) acrylate and hydroxy Examples include pivalate neopentyl glycol di (meth) acrylate.

分子内に1個の(メタ)アクリロイル基を有する単量体として、例えば、イソボルニルオキシエチル(メタ)アクリレート、イソボルニル(メタ)アクリレート、2−エチルヘキシル(メタ)アクリレート、エチルジエチレングリコール(メタ)アクリレート、ラウリル(メタ)アクリレート、ジシクロペンタジエン(メタ)アクリレート、ジシクロペンテニルオキシエチル(メタ)アクリレート、ジシクロペンテニル(メタ)アクリレート、N,N−ジメチル(メタ)アクリルアミド、テトラクロロフェニル(メタ)アクリレート、2−テトラクロロフェノキシエチル(メタ)アクリレート、テトラヒドロフルフリル(メタ)アクリレート、2−トリクロロフェノキシエチル(メタ)アクリレート、トリブロモフェニル(メタ)アクリレート、2−ヒドロキシエチル(メタ)アクリレート、2−ヒドロキシプロピル(メタ)アクリレート、2−ヒドロキシブチル(メタ)アクリレート、フェノキシエチル(メタ)アクリレート、ブトキシエチル(メタ)アクリレート、ペンタクロロフェニル(メタ)アクリレート、ポリエチレングリコールモノ(メタ)アクリレート、ポリプロピレングリコールモノ(メタ)アクリレート、ボルニル(メタ)アクリレート、1,4−ブタンジオールモノ(メタ)アクリレート、2−エチルヘキシルポリオキシ(メタ)アクリレート、ベンジル(メタ)アクリレート、トリシクロデカンモノ(メタ)アクリレート、2−(メタ)アクリロイロキシエチルコハク酸、2−(メタ)アクリロイロキシエチルへキサヒドロフタル酸、エトキシジエチレングリコール(メタ)アクリレート、メトキシトリエチレングリコール(メタ)アクリレート及び2−メタクリロイロキシエチル−2−ヒドロキシエチルフタル酸が挙げられる。   As a monomer having one (meth) acryloyl group in the molecule, for example, isobornyloxyethyl (meth) acrylate, isobornyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, ethyldiethylene glycol (meth) acrylate , Lauryl (meth) acrylate, dicyclopentadiene (meth) acrylate, dicyclopentenyloxyethyl (meth) acrylate, dicyclopentenyl (meth) acrylate, N, N-dimethyl (meth) acrylamide, tetrachlorophenyl (meth) acrylate, 2-tetrachlorophenoxyethyl (meth) acrylate, tetrahydrofurfuryl (meth) acrylate, 2-trichlorophenoxyethyl (meth) acrylate, tribromophenyl (meth) acrylate 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 2-hydroxybutyl (meth) acrylate, phenoxyethyl (meth) acrylate, butoxyethyl (meth) acrylate, pentachlorophenyl (meth) acrylate, polyethylene Glycol mono (meth) acrylate, polypropylene glycol mono (meth) acrylate, bornyl (meth) acrylate, 1,4-butanediol mono (meth) acrylate, 2-ethylhexyl polyoxy (meth) acrylate, benzyl (meth) acrylate, tri Cyclodecane mono (meth) acrylate, 2- (meth) acryloyloxyethyl succinic acid, 2- (meth) acryloyloxyethylhexahydrophthalic acid, ethoxydiethylene glycol Call (meth) acrylate, methoxy triethylene glycol (meth) acrylate and 2-methacryloyloxyethyl-2-hydroxyethyl phthalate.

上述した(a2)成分は、1種又は2種以上を組み合わせて使用してもよい。これらの中でも、硬化被膜(A)と樹脂基材の密着性を高める点で、1,6−ヘキサンジオールジ(メタ)アクリレートが好ましい。   The component (a2) described above may be used alone or in combination of two or more. Among these, 1,6-hexanediol di (meth) acrylate is preferable in terms of enhancing the adhesion between the cured coating (A) and the resin substrate.

(a2)成分の含有量は特に制限されるものではないが、(a1)成分及び(a2)成分を含む硬化性組成物の総重量100質量%に対して10質量%以上50質量%以下とすることができる。(a2)成分の含有量の下限は、(a1)成分及び(a2)成分を含む硬化性組成物を硬化させる際の硬化収縮率が低下し、硬化被膜(A)の耐クラック性が良好となる傾向にあり、樹脂基材に対する硬化被膜(A)の密着性が良好となり、また、樹脂基材の表面に硬化被膜(A)を積層した樹脂積層体の反りを抑制できる観点から、10質量%以上が好ましく、15質量%以上がより好ましく、25質量%以上がさらに好ましい。(a2)成分の含有量の上限は、硬化被膜(A)の耐擦傷性及び表面硬度が良好となる観点から50質量%以下が好ましく、40質量%以下がより好ましく、35質量%以下がさらに好ましい。   The content of the component (a2) is not particularly limited, but is 10% by mass to 50% by mass with respect to 100% by mass of the total weight of the curable composition containing the component (a1) and the component (a2). can do. The lower limit of the content of the component (a2) is that the curing shrinkage rate when the curable composition containing the component (a1) and the component (a2) is cured decreases, and the crack resistance of the cured film (A) is good. From the viewpoint of improving the adhesion of the cured coating (A) to the resin substrate and suppressing the warpage of the resin laminate in which the cured coating (A) is laminated on the surface of the resin substrate. % Or more is preferable, 15 mass% or more is more preferable, and 25 mass% or more is more preferable. The upper limit of the content of the component (a2) is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less from the viewpoint of improving the scratch resistance and surface hardness of the cured film (A). preferable.

<その他の添加剤>
硬化被膜(A)の製造に用いられる前記硬化性組成物、又は後述する硬化被膜(B)の製造に用いられる硬化性組成物(s1)及び硬化性組成物(s2)は、必要に応じて有機溶剤、離型剤、滑剤、可塑剤、酸化防止剤、帯電防止剤、光安定剤、紫外線吸収剤、難燃剤、難燃助剤、重合禁止剤、充填剤、顔料、染料、シランカップリング剤、レベリング剤、消泡剤、蛍光剤、連鎖移動剤等の各種添加剤を含有することができる。
<Other additives>
The said curable composition used for manufacture of a cured film (A), or the curable composition (s1) and curable composition (s2) used for manufacture of the cured film (B) mentioned later are as needed. Organic solvents, mold release agents, lubricants, plasticizers, antioxidants, antistatic agents, light stabilizers, UV absorbers, flame retardants, flame retardant aids, polymerization inhibitors, fillers, pigments, dyes, silane couplings Various additives such as an agent, a leveling agent, an antifoaming agent, a fluorescent agent, and a chain transfer agent can be contained.

<重合開始剤>
硬化被膜(A)の製造に用いられる前記硬化性組成物、又は後述する硬化被膜(B)の製造に用いられる硬化性組成物(s1)及び硬化性組成物(s2)は、公知の重合開始剤を含有することができる。
<Polymerization initiator>
The curable composition used for the production of the cured film (A), or the curable composition (s1) and the curable composition (s2) used for the production of the cured film (B) described below, are known polymerization initiations. An agent can be contained.

重合開始剤としては、例えば、ベンゾフェノン、4,4’−ビス(ジエチルアミノ)ベンゾフェノン、2,4,6−トリメチルベンゾフェノン、メチルオルソベンゾイルベンゾエート、4−フェニルベンゾフェノン、t−ブチルアントラキノン、2−エチルアントラキノン、2−ヒドロキシ−2−メチル−1−フェニルプロパン−1−オン、ベンジルジメチルケタール、1−ヒドロキシシクロヘキシル−フェニルケトン、2−メチル−2−モルホリノ(4−チオメチルフェニル)プロパン−1−オン、2−ベンジル−2−ジメチルアミノ−1−(4−モルホリノフェニル)−ブタノン等のアセトフェノン類;ベンゾインメチルエーテル、ベンゾインエチルエーテル、ベンゾインイソプロピルエーテル、ベンゾインイソブチルエーテル等のベンゾインエーテル類;2,4,6−トリメチルベンゾイルジフェニルホスフィンオキサイド、ビス(2,6−ジメトキシベンゾイル)−2,4,4−トリメチルペンチルホスフィンオキサイド、等のアシルホスフィンオキサイド類;メチルベンゾイルホルメート;1,7−ビスアクリジニルヘプタン;及び9−フェニルアクリジンが挙げられる。これらは1種又は2種以上を組み合わせて使用することができる。   Examples of the polymerization initiator include benzophenone, 4,4′-bis (diethylamino) benzophenone, 2,4,6-trimethylbenzophenone, methyl orthobenzoylbenzoate, 4-phenylbenzophenone, t-butylanthraquinone, 2-ethylanthraquinone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyldimethyl ketal, 1-hydroxycyclohexyl-phenyl ketone, 2-methyl-2-morpholino (4-thiomethylphenyl) propan-1-one, 2 Acetophenones such as benzyl-2-dimethylamino-1- (4-morpholinophenyl) -butanone; benzene such as benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether Inethers; Acylphosphine oxides such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis (2,6-dimethoxybenzoyl) -2,4,4-trimethylpentylphosphine oxide; methylbenzoylformate; 1 , 7-bisacridinyl heptane; and 9-phenylacridine. These can be used alone or in combination of two or more.

重合開始剤の添加量は特に制限されるものではないが、硬化性組成物の硬化性を促進させる点で、該硬化性組成物の総重量100質量部(ただし、重合開始剤を除く。)に対して、0.1質量部以上10質量部以下が好ましく、0.1質量部以上5.0質量部以下がより好ましい。   The addition amount of the polymerization initiator is not particularly limited, but the total weight of the curable composition is 100 parts by mass (excluding the polymerization initiator) in terms of promoting the curability of the curable composition. Is preferably 0.1 parts by mass or more and 10 parts by mass or less, and more preferably 0.1 parts by mass or more and 5.0 parts by mass or less.

<硬化被膜(A)の形成方法>
硬化被膜(A)の形成方法としては、例えば、硬化被膜(A)の原料となる硬化性組成物を樹脂基材の表面に塗布した後に、前記硬化性組成物の塗膜を加熱すること又は塗膜に活性エネルギー線を照射する方法が挙げられる。
<Method for forming cured coating (A)>
As a method for forming the cured film (A), for example, after applying a curable composition as a raw material of the cured film (A) to the surface of the resin substrate, the coating film of the curable composition is heated or The method of irradiating an active energy ray to a coating film is mentioned.

本発明の硬化被膜(A)は、樹脂基材の第1面、又は第1面及び第2面に積層することができ、目的に応じて選択することができる。樹脂基材の第2面とは、樹脂基材において樹脂基材の第1面に対向する面のことをいう。   The cured coating (A) of this invention can be laminated | stacked on the 1st surface of a resin base material, or a 1st surface and a 2nd surface, and can be selected according to the objective. The 2nd surface of a resin base material means the surface which opposes the 1st surface of a resin base material in a resin base material.

樹脂基材の表面への硬化性組成物の塗布方法としては、例えば、流延法、ローラーコート法、バーコート法、噴霧コート法及びエアーナイフコート法が挙げられる。   Examples of the method for applying the curable composition to the surface of the resin substrate include a casting method, a roller coating method, a bar coating method, a spray coating method, and an air knife coating method.

硬化被膜(A)を樹脂基材の表面に積層する方法としては、例えば、以下の2つの方法が挙げられる。   Examples of the method for laminating the cured coating (A) on the surface of the resin substrate include the following two methods.

(1)樹脂基材の表面に硬化性組成物の塗膜を形成した後に、該硬化性組成物の塗膜を硬化させる方法。 (1) A method of curing a coating film of the curable composition after forming a coating film of the curable composition on the surface of the resin substrate.

(2)鋳型の表面に硬化性組成物の塗膜を形成した後に、該硬化性組成物の塗膜を硬化させて、前記鋳型の表面に硬化被膜(A)が積層された型(1)を得る。次いで、前記型(1)と、他の鋳型(型(2))とを、前記硬化被膜(A)が内側になるように対向させて空間を形成するように配置して積層鋳型とする。次いで、前記積層鋳型の空間に樹脂基材原料を流し込み、該樹脂基材原料を注型重合した後に、前記2つの鋳型を除去する方法 (2) A mold (1) in which a coating film of a curable composition is formed on the surface of a mold, and then a coating film of the curable composition is cured, and a cured film (A) is laminated on the surface of the mold Get. Next, the mold (1) and another mold (mold (2)) are arranged so as to face each other so that the cured coating (A) is on the inside, thereby forming a laminated mold. Next, a method of removing the two molds after pouring a resin base material into the space of the laminated mold, cast polymerizing the resin base material

上記の方法の中で、(2)の方法は、高い鉛筆硬度を有する硬化被膜(A)が得られる点から好ましい。   Among the above methods, the method (2) is preferable from the viewpoint of obtaining a cured film (A) having high pencil hardness.

(1)及び(2)の方法で硬化性組成物を硬化するに際して、異物等による欠陥が無い良好な外観を有する硬化被膜(A)を得るために、硬化性組成物の塗膜の表面を後述する樹脂フィルムで被覆することができる。また、樹脂フィルムで硬化性組成物の表面を覆った後、JIS K 6253に準拠した硬度40°のゴムロール等のロールを用いて樹脂フィルム面に対して平滑処理を施すことができる。ロールによる平滑処理により、より均一な膜厚の硬化被膜(A)を得ることができ、高い平滑性と所望の膜厚を有する硬化被膜を得ることができる傾向にある。また、硬化性組成物として活性エネルギー線硬化性組成物を使用する場合、樹脂フィルムで硬化性組成物の表面を被覆した後に活性エネルギー線を照射することにより、硬化性組成物の架橋反応が充分に進行して硬化度の良好な硬化被膜が得られる傾向にあり、硬化被膜(A)の耐擦傷性及び表面硬度が良好となる傾向にある。   When the curable composition is cured by the methods (1) and (2), the surface of the coating film of the curable composition is obtained in order to obtain a cured film (A) having a good appearance free from defects due to foreign matters and the like. It can coat | cover with the resin film mentioned later. Moreover, after covering the surface of the curable composition with a resin film, the resin film surface can be smoothed using a roll such as a rubber roll having a hardness of 40 ° in accordance with JIS K 6253. By the smoothing treatment with a roll, a cured film (A) having a more uniform film thickness can be obtained, and a cured film having high smoothness and a desired film thickness tends to be obtained. Moreover, when using an active energy ray curable composition as a curable composition, the crosslinking reaction of a curable composition is enough by irradiating an active energy ray after coat | covering the surface of a curable composition with a resin film. The cured film having a good curing degree tends to be obtained, and the scratch resistance and surface hardness of the cured film (A) tend to be good.

<樹脂フィルム>
硬化被膜(A)の製造に用いられる樹脂フィルムとしては、例えば、ポリエチレンテレフタレート(PET)フィルム、ポリプロピレン(PP)フィルム、ポリエチレン(PE)フィルム及びポリフッ化ビニリデン(PVDF)フィルムが挙げられる。これらの中で、コスト及び硬化性組成物の硬化性の点で、PETフィルムが好ましい。
<Resin film>
As a resin film used for manufacture of a cured film (A), a polyethylene terephthalate (PET) film, a polypropylene (PP) film, a polyethylene (PE) film, and a polyvinylidene fluoride (PVDF) film are mentioned, for example. Among these, a PET film is preferable in terms of cost and curability of the curable composition.

樹脂フィルムの厚みとしては、樹脂フィルムの強度、取り扱い性及びコストの点で、8μm以上125μm以下が好ましい。   The thickness of the resin film is preferably 8 μm or more and 125 μm or less in terms of the strength, handleability and cost of the resin film.

<活性エネルギー線>
硬化性組成物を活性エネルギー線で硬化する場合、活性エネルギー線としては、例えば、電子線、紫外線及び可視光線が挙げられるが、装置コストや生産性の観点から紫外線が好ましい。
<Active energy rays>
When the curable composition is cured with an active energy ray, examples of the active energy ray include an electron beam, an ultraviolet ray and a visible ray, and an ultraviolet ray is preferable from the viewpoint of apparatus cost and productivity.

活性エネルギー線の光源としては、例えば、蛍光紫外線ランプ、超高圧水銀ランプ、高圧水銀ランプ、中圧水銀ランプ、低圧水銀ランプ、メタルハライドランプ、Arレーザー、He−Cdレーザー、固体レーザー、キセノンランプ、高周波誘導水銀ランプ及び太陽光が挙げられる。これらの中で、硬化性組成物(a)の硬化速度の点で、蛍光紫外線ランプ及び高圧水銀灯が好ましい。活性エネルギー線の積算光量としては、5mJ/cm2以上2,000mJ/cm2以下が好ましい。 Examples of the active energy ray light source include a fluorescent ultraviolet lamp, an ultrahigh pressure mercury lamp, a high pressure mercury lamp, a medium pressure mercury lamp, a low pressure mercury lamp, a metal halide lamp, an Ar laser, a He-Cd laser, a solid laser, a xenon lamp, and a high frequency. Examples include induction mercury lamps and sunlight. Among these, a fluorescent ultraviolet lamp and a high-pressure mercury lamp are preferable from the viewpoint of the curing rate of the curable composition (a). The integrated light quantity of the active energy ray, 5 mJ / cm 2 or more 2,000 mJ / cm 2 or less.

<硬化被膜(B)>
硬化被膜(B)は、本発明の樹脂積層体を構成する構成要素の1つで、樹脂基材の第1面に積層された硬化被膜(A)における、樹脂基材と接する面と対向する面に形成されているものである。
<Hardened film (B)>
The cured coating (B) is one of the components constituting the resin laminate of the present invention, and faces the surface in contact with the resin substrate in the cured coating (A) laminated on the first surface of the resin substrate. It is formed on the surface.

本発明において、硬化被膜(A)が樹脂基材の第1面及び第2面に積層されている場合、硬化被膜(B)は樹脂基材の第1面に積層された硬化被膜(A)のみに積層されていても、樹脂基材の第1面及び第2面に積層された硬化被膜(A)の両方に積層されていてもよく、目的に応じて選択することができる。   In the present invention, when the cured coating (A) is laminated on the first surface and the second surface of the resin substrate, the cured coating (B) is a cured coating (A) laminated on the first surface of the resin substrate. Even if it is laminated | stacked only on it, it may be laminated | stacked on both of the cured film (A) laminated | stacked on the 1st surface and 2nd surface of the resin base material, and it can select according to the objective.

本発明の樹脂積層体において、硬化被膜(B)は、鉛筆硬度が8H以上であり、ISO2409:1992に準拠したクロスカット剥離試験による硬化被膜(B)の残存率が80%以上である。また、硬化被膜(B)の表面の鉛筆硬度を8H以上とすることにより、樹脂積層体の表面に指の爪等による引掻き傷の発生を抑制でき、耐擦傷性の良好な樹脂積層体とすることができる。   In the resin laminate of the present invention, the cured film (B) has a pencil hardness of 8H or more, and the residual rate of the cured film (B) by a cross-cut peel test in accordance with ISO 2409: 1992 is 80% or more. Further, by setting the pencil hardness of the surface of the cured coating (B) to 8H or more, it is possible to suppress the occurrence of scratches caused by finger nails on the surface of the resin laminate, and to obtain a resin laminate having good scratch resistance. be able to.

本発明の樹脂積層体において、硬化被膜(B)は、低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層から選ばれる1つの機能を有する機能層である硬化被膜(B´)、又は、硬化被膜(A)と後述する機能層(C)を接着させる接着層の硬化被膜(B´´)である。   In the resin laminate of the present invention, the cured coating (B) is a functional layer having one function selected from a low refractive index layer, a high refractive index layer, a hard coat layer, an antistatic layer, an antiglare layer and an antifouling layer. Is a cured film (B ′), or a cured film (B ″) of an adhesive layer that bonds the cured film (A) and a functional layer (C) described later.

前記硬化被膜(B´)の膜厚は、特に制限されるものではないが、0.6μm以上3μm以下が好ましい。硬化被膜(B´)の膜厚の下限は、硬化被膜の耐擦傷性及び表面硬度が良好となる観点から0.6μm以上が好ましく、1μm以上がより好ましい。また、膜厚の上限は、硬化被膜(A)との密着性が向上する観点から3μm以下が好ましく、2μm以下がより好ましい。即ち、硬化被膜(B)の膜厚は、1μm以上2μm以下が好ましい。   The film thickness of the cured coating (B ′) is not particularly limited, but is preferably 0.6 μm or more and 3 μm or less. The lower limit of the film thickness of the cured film (B ′) is preferably 0.6 μm or more and more preferably 1 μm or more from the viewpoint of good scratch resistance and surface hardness of the cured film. Further, the upper limit of the film thickness is preferably 3 μm or less, more preferably 2 μm or less, from the viewpoint of improving the adhesion with the cured coating (A). That is, the film thickness of the cured coating (B) is preferably 1 μm or more and 2 μm or less.

前記硬化被膜(B´´)の膜厚は、特に制限されるものではないが、3μm以上7μm以下が好ましい。硬化被膜(B´)の膜厚の下限は、硬化被膜の外観が良好となる観点から3μm以上が好ましく、4μm以上がより好ましい。また、膜厚の上限は、硬化被膜(A)及び後述する機能層(C)との密着性が向上する観点から7μm以下が好ましく、6.5μm以下がより好ましい。即ち、硬化被膜(B)の膜厚は4μm以上6.5μm以下がより好ましい。   The film thickness of the cured coating (B ″) is not particularly limited, but is preferably 3 μm or more and 7 μm or less. The lower limit of the film thickness of the cured film (B ′) is preferably 3 μm or more, and more preferably 4 μm or more, from the viewpoint of improving the appearance of the cured film. Further, the upper limit of the film thickness is preferably 7 μm or less, and more preferably 6.5 μm or less from the viewpoint of improving the adhesion between the cured film (A) and the functional layer (C) described later. That is, the thickness of the cured coating (B) is more preferably 4 μm or more and 6.5 μm or less.

ここでいう硬化被膜(B)の膜厚とは、樹脂積層体における硬化被膜(B)の膜厚のことをいう。硬化被膜(B)の厚みは、厚み方向にミクロトームで幅100nmのサンプルを切り出し、透過型電子顕微鏡(日本電子(株)製JEM−1010(商品名))で樹脂積層体の断面を観察した。   The film thickness of the cured film (B) here refers to the film thickness of the cured film (B) in the resin laminate. Regarding the thickness of the cured coating (B), a sample having a width of 100 nm was cut out with a microtome in the thickness direction, and a cross section of the resin laminate was observed with a transmission electron microscope (JEM-1010 (trade name) manufactured by JEOL Ltd.).

<硬化性組成物(s1)>
本発明において、硬化性組成物(s1)は前記硬化被膜(B´)を得るために使用される原料である。
<Curable composition (s1)>
In this invention, a curable composition (s1) is a raw material used in order to obtain the said cured film (B ').

硬化性組成物(s1)としては、例えば、後述する(b1)成分、後述する(b2−1)成分及び後述する(b2−2)成分の少なくとも1種類、後述する有機溶剤(b4)、後述する重合開始剤を含有する組成物が挙げられる。   Examples of the curable composition (s1) include at least one of a component (b1) described later, a component (b2-1) described later, and a component (b2-2) described later, an organic solvent (b4) described later, And a composition containing a polymerization initiator.

さらに、前記硬化性組成物(s1)の粘度を下げる目的で、分子中に1個又は2個の(メタ)アクリロイルオキシ基を有する単量体から選ばれる少なくとも1種の単量体を添加することができる。具体的には、上述した(a2)成分と同様のものが挙げられる。これらは1種又は2種以上を組み合わせて使用することができる。   Furthermore, for the purpose of lowering the viscosity of the curable composition (s1), at least one monomer selected from monomers having one or two (meth) acryloyloxy groups in the molecule is added. be able to. Specifically, the same thing as the component (a2) mentioned above is mentioned. These can be used alone or in combination of two or more.

<硬化性組成物(s2)>
本発明において、硬化性組成物(s2)は前記硬化被膜(B´´)を得るために使用される原料である。
<Curable composition (s2)>
In the present invention, the curable composition (s2) is a raw material used for obtaining the cured film (B ″).

硬化性組成物(s2)としては、例えば、後述する(b1)成分、後述する(b2−1)成分及び後述する(b2−2)成分の少なくとも1種類、後述する無機微粒子(b3)、後述する重合開始剤を含有する組成物が挙げられる。   Examples of the curable composition (s2) include at least one of a component (b1) described later, a component (b2-1) described later, and a component (b2-2) described later, inorganic fine particles (b3) described later, And a composition containing a polymerization initiator.

さらに、前記硬化性組成物(s2)の粘度を下げる目的で、分子中に1個又は2個の(メタ)アクリロイルオキシ基を有する単量体から選ばれる少なくとも1種の単量体を添加することができる。具体的には、上述した(a2)成分と同様のものが挙げられる。これらは1種又は2種以上を組み合わせて使用することができる。   Furthermore, for the purpose of lowering the viscosity of the curable composition (s2), at least one monomer selected from monomers having one or two (meth) acryloyloxy groups in the molecule is added. be able to. Specifically, the same thing as the component (a2) mentioned above is mentioned. These can be used alone or in combination of two or more.

<(b1)成分>
本発明において、(b1)成分は、分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位を構成する単量体のことをいう。(b1)成分は、硬化被膜(B)の硬度を向上させることにより、樹脂積層体の耐擦傷性及び表面硬度を向上させる効果を有する。
<(B1) component>
In the present invention, the component (b1) refers to a monomer constituting a repeating unit derived from a monomer having three or more (meth) acryloyloxy groups in the molecule. The component (b1) has the effect of improving the scratch resistance and surface hardness of the resin laminate by improving the hardness of the cured coating (B).

(b1)成分としては、前記(a1)成分に記載した単量体と同様のものが挙げられ、例えば、(メタ)アクリロイルオキシ基を一分子中に3個以上20個以下有する単量体が挙げられる。これらは1種又は2種以上を組み合わせて使用することができる。   Examples of the component (b1) include the same monomers as those described in the component (a1). For example, a monomer having 3 to 20 (meth) acryloyloxy groups in one molecule. Can be mentioned. These can be used alone or in combination of two or more.

(b1)成分としては、トリメチロールプロパントリアクリレート、ジトリメチロールプロパンテトラ(メタ)アクリレート、ペンタエリスリトールトリ(メタ)アクリレート、ペンタエリスリトールテトラ(メタ)アクリレート、ジペンタエリスリトールペンタ(メタ)アクリレート、ジペンタエリスリトールヘキサ(メタ)アクリレートが好ましい。   As component (b1), trimethylolpropane triacrylate, ditrimethylolpropane tetra (meth) acrylate, pentaerythritol tri (meth) acrylate, pentaerythritol tetra (meth) acrylate, dipentaerythritol penta (meth) acrylate, dipentaerythritol Hexa (meth) acrylate is preferred.

<(b2−1)成分>
本発明において、(b2−1)成分は、ウレタン(メタ)アクリレート由来の繰り返し単位を構成する単量体のことをいう。(b2−1)成分は硬化被膜(B)と硬化被膜(A)との密着性を向上させ、また樹脂積層体の耐擦傷性及び表面硬度を向上させる効果を有する。
<(B2-1) component>
In the present invention, the component (b2-1) refers to a monomer that constitutes a repeating unit derived from urethane (meth) acrylate. The component (b2-1) has an effect of improving the adhesion between the cured film (B) and the cured film (A) and improving the scratch resistance and surface hardness of the resin laminate.

(b2−1)成分としては、例えば、1,5−ジイソシアナトペンタン、1,6−ジイソシアナトヘキサン、1,4−ジイソシアナトペンタン、1,6−ジイソシアナト−3,5,5−トリメチルヘキサン、1,6−ジイソシアナト−3,3,5−トリメチルヘキサン、1,12−ジイソシアナトドデカン、1,8−ジイソシアナト−4−イソシアナトメチルオクタン、1,3,6−トリイソシアナトヘキサン、1,6,11−トリイソシアナトウンデカン、ヘキサメチレンジイソシアネート、イソホロンジイソシアネート、トリレンジイソシアネート、1,2−キシリレンジイソシアネート、1,4−キシリレンジイソシアネート、1,2−水添キシリレンジイソシアネート、1,4−水添キシリレンジイソシアネート、テトラメチルキシリレンジイソシアネート、ジフェニルメタンジイソシアネート、水添ジフェニルメタンジイソシアネート、ナフタレンジイソシアネート、ノルボルナンジイソシアネート等のイソシアネート化合物と、ポリエチレングリコール(繰返し単位=6〜20)、ポリプロピレングリコール(繰返し単位=6〜20)、ポリブチレングリコール(繰返し単位=6〜20)1−メチルブチレングリコール(繰り返し単位=6〜20)、ポリテトラメチレングリコール(繰返し単位=6〜20)、ポリカプロラクトンジオール、アルキレン(炭素数2〜10)ジオールのカプロラクトン付加(繰返し単位=2〜10)ジオール、ビスフェノールAのエチレンオキサイド付加物、ビスフェノールAのプロピレンオキサイド付加物、フタル酸とアルキレンジオールから誘導されたポリエステルジオール、ポリカーボネートジオール(炭素数4〜6の脂肪族骨格)等のポリオール化合物と、2−ヒドロキシエチル(メタ)アクリレート、2−ヒドロキシプロピル(メタ)アクリレート、4−ヒドロキシブチル(メタ)アクリレート、ポリエチレングリコールモノ(メタ)アクリレート、ポリプロピレングリコールモノ(メタ)アクリレート、N−ヒドロキシエチル−N’,N”−ジ((メタ)アクリロキシエトキシエチル)イソシアヌレート等の水酸基を有する(メタ)アクリレートを反応させたウレタン(メタ)アクリレート;ヘキサメチレンジイソシアネート、イソホロンジイソシアネート、トリレンジイソシアネート、1,2−キシリレンジイソシアネート、1,4−キシリレンジイソシアネート、1,2−水添キシリレンジイソシアネート、1,4−水添キシリレンジイソシアネート、テトラメチルキシリレンジイソシアネート、ジフェニルメタンジイソシアネート、水添ジフェニルメタンジイソシアネート、ナフタレンジイソシアネート、ノルボルナンジイソシアネート等のイソシアネート化合物やそれらの多量体に、2−ヒドロキシエチル(メタ)アクリレート、2−ヒドロキシプロピル(メタ)アクリレート、4−ヒドロキシブチル(メタ)アクリレートやそれらのカプロラクトン付加体等の水酸基を有する(メタ)アクリレートを付加したウレタンポリ(メタ)アクリレート;1,5−ジイソシアナトペンタン、1,6−ジイソシアナトヘキサン(HDI)、1,4−ジイソシアナトペンタン、1,6−ジイソシアナト−3,5,5−トリメチルヘキサン、1,6−ジイソシアナト−3,3,5−トリメチルヘキサン、1,12−ジイソシアナトドデカン、1,8−ジイソシアナト−4−イソシアナトメチルオクタン、1,3,6−トリイソシアナトヘキサン、1,6,11−トリイソシアナトウンデカンヘキサン、イソホロンジイソシアネート、トリレンジイソシアネート、キシリレンジイソシアネート、水添キシリレンジイソシアネート、テトラメチルキシリレンジイソシアネート、ジフェニルメタンジイソシアネート、水添ジフェニルメタンジイソシアネート、ナフタレンジイソシアネート、ノルボルナンジイソシアネート、デカリンジイソシアネート、リジンジイソシアネート、リジントリイソシアネート等のイソシアネート化合物の単量体または多量体に、2−ヒドロキシエチル(メタ)アクリレート、2−ヒドロキシプロピル(メタ)アクリレート、4―ヒドロキシブチル(メタ)アクリレートやそれらのカプロラクトン付加体等の水酸基を有する(メタ)アクリレートを付加したウレタン(メタ)アクリレート等が挙げられる。   Examples of the component (b2-1) include 1,5-diisocyanatopentane, 1,6-diisocyanatohexane, 1,4-diisocyanatopentane, 1,6-diisocyanato-3,5,5- Trimethylhexane, 1,6-diisocyanato-3,3,5-trimethylhexane, 1,12-diisocyanatododecane, 1,8-diisocyanato-4-isocyanatomethyloctane, 1,3,6-triisocyanatohexane 1,6,11-triisocyanatoundecane, hexamethylene diisocyanate, isophorone diisocyanate, tolylene diisocyanate, 1,2-xylylene diisocyanate, 1,4-xylylene diisocyanate, 1,2-hydrogenated xylylene diisocyanate, 1, , 4-Hydrogenated xylylene diisocyanate, tetramethyloxy Isocyanate compounds such as diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, norbornane diisocyanate, polyethylene glycol (repeating unit = 6-20), polypropylene glycol (repeating unit = 6-20), polybutylene glycol (repeating unit) = 6-20) 1-methylbutylene glycol (repeating unit = 6-20), polytetramethylene glycol (repeating unit = 6-20), polycaprolactone diol, caprolactone addition of alkylene (2-10 carbon atoms) diol (repeating) Unit = 2 to 10) Diol, bisphenol A ethylene oxide adduct, bisphenol A propylene oxide adduct, phthalic acid and alkylenediode Polyol compounds such as polyester diols and polycarbonate diols (aliphatic skeleton having 4 to 6 carbon atoms) derived from ruthenium, 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 4-hydroxybutyl ( Having a hydroxyl group such as (meth) acrylate, polyethylene glycol mono (meth) acrylate, polypropylene glycol mono (meth) acrylate, N-hydroxyethyl-N ′, N ″ -di ((meth) acryloxyethoxyethyl) isocyanurate (meta ) Urethane (meth) acrylate reacted with acrylate; hexamethylene diisocyanate, isophorone diisocyanate, tolylene diisocyanate, 1,2-xylylene diisocyanate, 1,4-xylylene diisocyanate, 1 , 2-hydrogenated xylylene diisocyanate, 1,4-hydrogenated xylylene diisocyanate, tetramethyl xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, norbornane diisocyanate -Urethane poly (meth) acrylate added with (meth) acrylate having a hydroxyl group such as hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate and their caprolactone adducts; 1,5-diisocyanatopentane, 1,6-diisocyanatohexane (HDI), 1,4-diisocyanatopentane, 1,6-diisocyanato-3,5, -Trimethylhexane, 1,6-diisocyanato-3,3,5-trimethylhexane, 1,12-diisocyanatododecane, 1,8-diisocyanato-4-isocyanatomethyloctane, 1,3,6-triisocyanato Hexane, 1,6,11-triisocyanatoundecane hexane, isophorone diisocyanate, tolylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, tetramethyl xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, norbornane diisocyanate , A monomer or multimer of an isocyanate compound such as decalin diisocyanate, lysine diisocyanate, lysine triisocyanate, Examples include urethane (meth) acrylate added with (meth) acrylate having a hydroxyl group such as hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate and caprolactone adducts thereof. It is done.

(b1)成分の他の例としては、下式(I)で示されるポリイソシアネート1モルに対して、2−ヒドロキシエチル(メタ)アクリレート、2−ヒドロキシプロピル(メタ)アクリレート、2−ヒドロキシ−3−メトキシプロピル(メタ)アクリレート、N−メチロール(メタ)アクリルアミド、N−ヒドロキシ(メタ)アクリルアミド等の活性水素を有するアクリルモノマー3モル以上を反応させて得られるウレタン(メタ)アクリレート;トリス(2−ヒドロキシエチル)イソシアヌル酸のトリ(メタ)アクリレート等のポリ[(メタ)アクリロイルオキシエチル]イソシアヌレート;エポキシポリ(メタ)アクリレート;及びウレタンポリ(メタ)アクリレートが挙げられる。   Other examples of the component (b1) include 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, and 2-hydroxy-3 with respect to 1 mol of the polyisocyanate represented by the following formula (I). -Urethane (meth) acrylate obtained by reacting 3 mol or more of an acrylic monomer having active hydrogen such as methoxypropyl (meth) acrylate, N-methylol (meth) acrylamide, N-hydroxy (meth) acrylamide, etc .; Tris (2- And poly [(meth) acryloyloxyethyl] isocyanurate such as tri (meth) acrylate of hydroxyethyl) isocyanuric acid; epoxy poly (meth) acrylate; and urethane poly (meth) acrylate.

(I)
(式(I)中、Rは置換基を含んでも良い、炭素数1〜12の2価の炭化水素基を表す。)
(I)
(In formula (I), R represents a divalent hydrocarbon group having 1 to 12 carbon atoms which may contain a substituent.)

式(I)で示されるポリイソシアネートとしては、トリメチロールプロパントルイレンジイソシアネート、ヘキサメチレンジイソシアネート、トリレンジイソシアネート、ジフェニルメタンジイソシアネート、キシレンジイソシアネート、4,4’−メチレンビス(シクロヘキシルイソシアネート)、イソホロンジイソシアネート、トリメチルヘキサメチレンジイソシアネート等のイソシアネート化合物の3量化により得られるポリイソシアネートが好ましい。これらは、一種を単独で、又は二種以上を併用して用いることができる。   Examples of the polyisocyanate represented by the formula (I) include trimethylolpropane toluylene diisocyanate, hexamethylene diisocyanate, tolylene diisocyanate, diphenylmethane diisocyanate, xylene diisocyanate, 4,4′-methylenebis (cyclohexyl isocyanate), isophorone diisocyanate, trimethylhexamethylene. Polyisocyanates obtained by trimerization of isocyanate compounds such as diisocyanate are preferred. These can be used individually by 1 type or in combination of 2 or more types.

(b2−1)成分としては、3個以上の(メタ)アクリロイルオキシ基を有するウレタン(メタ)アクリレートが好ましく、6個以上の(メタ)アクリロイルオキシ基を有するウレタン(メタ)アクリレートがさらに好ましい。   As the component (b2-1), a urethane (meth) acrylate having 3 or more (meth) acryloyloxy groups is preferable, and a urethane (meth) acrylate having 6 or more (meth) acryloyloxy groups is more preferable.

<(b2−2)成分>
本発明において、(b2−2)成分は、アミノ基を有する(メタ)アクリレート由来の繰り返し単位を構成する単量体のことをいう。(b2−2)成分は、硬化被膜(B)と硬化被膜(A)との密着性を向上させ、また樹脂積層体の耐擦傷性及び表面硬度を向上させる効果を有する。
<(B2-2) component>
In the present invention, the component (b2-2) refers to a monomer constituting a repeating unit derived from a (meth) acrylate having an amino group. The component (b2-2) has an effect of improving the adhesion between the cured coating (B) and the cured coating (A) and improving the scratch resistance and surface hardness of the resin laminate.

(b2−2)成分としては、例えば、アクリルアミド、7−アミノ−3,7−ジメチルオクチル(メタ)アクリレート、t−オクチル(メタ)アクリルアミド、ジアセトン(メタ)アクリルアミド、ジメチルアミノエチル(メタ)アクリレート、ジエチルアミノエチル(メタ)アクリレート、N,N−ジメチル(メタ)アクリルアミド、N,N−ジエチルアミノエチル(メタ)アクリレート、テトラクロロフェニル(メタ)アクリレート、N−ビニルホルムアミド、N−n−ブトキシメチル(メタ)アクリルアミド、N−イソブトキシメチル(メタ)アクリルアミド、N−メトキシメチル(メタ)アクリルアミド及び(メタ)アクリロイルモルフォリンが挙げられる。これらは1種又は2種以上を組み合わせて使用することができる。   Examples of the component (b2-2) include acrylamide, 7-amino-3,7-dimethyloctyl (meth) acrylate, t-octyl (meth) acrylamide, diacetone (meth) acrylamide, dimethylaminoethyl (meth) acrylate, Diethylaminoethyl (meth) acrylate, N, N-dimethyl (meth) acrylamide, N, N-diethylaminoethyl (meth) acrylate, tetrachlorophenyl (meth) acrylate, N-vinylformamide, Nn-butoxymethyl (meth) acrylamide N-isobutoxymethyl (meth) acrylamide, N-methoxymethyl (meth) acrylamide and (meth) acryloylmorpholine. These can be used alone or in combination of two or more.

上述した(b2−1)成分、(b2−2)成分の合計含有量は特に制限されるものではないが、硬化性組成物(s1)又は硬化性組成物(s2)の固形分を100質量%(ただし、重合開始剤を除く。)として、1.0質量%以上15質量%以下とすることができる。含有量の下限は、硬化被膜(A)に対する硬化被膜(B)の密着性が良好となる観点から1.0%以上が好ましく、2.2質量%以上がより好ましい。含有量の上限は、硬化被膜(B)の耐擦傷性及び表面硬度が良好となる観点から15質量%以下が好ましく、10質%以下がより好ましい。   The total content of the component (b2-1) and the component (b2-2) described above is not particularly limited, but the solid content of the curable composition (s1) or the curable composition (s2) is 100 masses. % (However, excluding the polymerization initiator) can be 1.0% by mass or more and 15% by mass or less. The lower limit of the content is preferably 1.0% or more and more preferably 2.2% by mass or more from the viewpoint of good adhesion of the cured film (B) to the cured film (A). The upper limit of the content is preferably 15% by mass or less and more preferably 10% by mass or less from the viewpoint of improving the scratch resistance and surface hardness of the cured coating (B).

<(b3)成分>
本発明において、(b3)成分は、無機微粒子のことをいう。硬化性組成物(s2)が無機微粒子(b3)を含有することにより、硬化被膜(A)に対する硬化被膜(B´´)の密着性を向上させ、また、硬化被膜(B)の耐擦傷性を向上させることができる。
<(B3) component>
In the present invention, the component (b3) refers to inorganic fine particles. When the curable composition (s2) contains the inorganic fine particles (b3), the adhesion of the cured coating (B ″) to the cured coating (A) is improved, and the scratch resistance of the cured coating (B). Can be improved.

(b3)成分としては、例えば、アモルファスシリカ、結晶性シリカ、シリカ−アルミナ複合酸化物、カオリナイト、タルク、炭酸カルシウム(カルサイト型、バテライト型)、ゼオライト、アルミナ、ヒドロキシアパタイト等の無機粒子、架橋アクリル粒子、架橋PMMA粒子、架橋ポリスチレン粒子、ナイロン粒子、ポリエステル粒子、ベンゾグアナミン・ホルマリン縮合物粒子、ベンゾグアナミン・メラミン・ホルムアルデヒド縮合物粒子メラミン・ホルムアルデヒド縮合物粒子等の耐熱性高分子粒子及びシリカ・アクリル複合化合物等の有機・無機ハイブリッド微粒子が挙げられる。   Examples of the component (b3) include inorganic particles such as amorphous silica, crystalline silica, silica-alumina composite oxide, kaolinite, talc, calcium carbonate (calcite type, vaterite type), zeolite, alumina, hydroxyapatite, Heat-resistant polymer particles such as crosslinked acrylic particles, crosslinked PMMA particles, crosslinked polystyrene particles, nylon particles, polyester particles, benzoguanamine / formalin condensate particles, benzoguanamine / melamine / formaldehyde condensate particles, melamine / formaldehyde condensate particles, and silica / acrylic Organic / inorganic hybrid fine particles such as composite compounds are exemplified.

無機微粒子(b3)の形状としては、例えば、球状、塊状、板状、繊維状及びフレーク状が挙げられるが、これらの中で、分散性や他の部材に接触した際の粒子の脱落のし難さの点から球状の粒子が好ましい。   Examples of the shape of the inorganic fine particles (b3) include a spherical shape, a block shape, a plate shape, a fiber shape, and a flake shape. Among these, the dispersibility and the falling off of the particles when coming into contact with other members are included. From the viewpoint of difficulty, spherical particles are preferred.

無機微粒子(b3)の平均粒子径は特に制限されるものではないが、例えば、硬化被膜中の無機微粒子の分散性が良好となる観点から、平均粒子径1nm以上300nm以下とすることが好ましく、3nm以上100nm以下がより好ましい。   The average particle size of the inorganic fine particles (b3) is not particularly limited, but for example, from the viewpoint of good dispersibility of the inorganic fine particles in the cured film, the average particle size is preferably 1 nm to 300 nm, 3 nm or more and 100 nm or less are more preferable.

平均粒子径は、粒度分布測定装置SALD−7100(製品名、島津製作所(株)製)を用いて、JIS Z 8825−1準じて測定した値とする。   The average particle diameter is a value measured according to JIS Z 8825-1 using a particle size distribution analyzer SALD-7100 (product name, manufactured by Shimadzu Corporation).

(b3)成分の含有量は特に制限されるものではないが、硬化性組成物(s2)の固形分の総重量を100質量%(ただし、重合開始剤を除く。)として、1.0質量%以上10質量%以下とすることができる。(b3)成分の含有量の下限は硬化被膜(A)に対する硬化被膜(B)の密着性が良好となる観点から1.0質量%以上以上が好ましく、2.0質量%以上がより好ましい。(b3)成分の含有量の上限は、硬化被膜(B)の耐擦傷性が良好となる観点から10質量%以下が好ましく、7.5質量%以下がより好ましい。   The content of the component (b3) is not particularly limited, but is 1.0 mass when the total weight of the solid content of the curable composition (s2) is 100 mass% (excluding the polymerization initiator). % To 10% by mass. The lower limit of the content of the component (b3) is preferably 1.0% by mass or more, and more preferably 2.0% by mass or more from the viewpoint of good adhesion of the cured film (B) to the cured film (A). The upper limit of the content of the component (b3) is preferably 10% by mass or less and more preferably 7.5% by mass or less from the viewpoint of improving the scratch resistance of the cured coating (B).

<(b4)成分>
本発明において(b4)成分は、該硬化性組成物(s1)の粘度を下げて塗工性を向上する目的や前記硬化被膜(B´)と硬化被膜(A)との密着性を向上する目的、また硬化被膜(B´)の外観を良好とする目的で、前記硬化性組成物(s1)に少なくとも1種の有機溶剤のことをいう。
<(B4) component>
In the present invention, the component (b4) improves the coating property by reducing the viscosity of the curable composition (s1) and improves the adhesion between the cured coating (B ′) and the cured coating (A). For the purpose and the purpose of improving the appearance of the cured coating (B ′), it means at least one organic solvent in the curable composition (s1).

(b4)成分としては、例えば、炭化水素系溶剤等の非フッ素溶剤及び含フッ素溶剤が挙げられる。   Examples of the component (b4) include non-fluorine solvents such as hydrocarbon solvents and fluorine-containing solvents.

非フッ素溶剤の具体例としては、メチルエチルケトン、アセトン、メチルイソブチルケトン等のケトン類;エタノール、1−プロパノール、2−プロパノール、ブタノール、1−メトキシ−2プロパノール等の一価アルコール、エチレングリコール、ジエチレングリコール、プロピレングリコール等の多価アルコール等のアルコール類;酢酸エチル、酢酸ブチル、γ−ブチロラクトン等のエステル類;ジエチレングリコールモノメチルエーテル、ジエチレングリコールモノメチルエーテルアセテート、テトラヒドロフラン、1,4−ジオキサン等のエーテル類;トルエン、キシレン等の芳香族炭化水素類;及びジメチルホルムアミド、ジメチルアセトアミド、N−メチルピロリドン等のアミド類が挙げられる。   Specific examples of the non-fluorine solvent include ketones such as methyl ethyl ketone, acetone and methyl isobutyl ketone; monohydric alcohols such as ethanol, 1-propanol, 2-propanol, butanol and 1-methoxy-2propanol, ethylene glycol, diethylene glycol, Alcohols such as polyhydric alcohols such as propylene glycol; esters such as ethyl acetate, butyl acetate and γ-butyrolactone; ethers such as diethylene glycol monomethyl ether, diethylene glycol monomethyl ether acetate, tetrahydrofuran and 1,4-dioxane; toluene, xylene And aromatic amides such as dimethylformamide, dimethylacetamide, N-methylpyrrolidone and the like.

含フッ素溶剤の具体例としては、含フッ素アルコール、含フッ素エーテル、ハイドロフルオロカーボン及びジトリフルオロメチルベンゼンが挙げられる。   Specific examples of the fluorine-containing solvent include fluorine-containing alcohols, fluorine-containing ethers, hydrofluorocarbons, and ditrifluoromethylbenzene.

含フッ素アルコールの具体例としては、H(CF2)m(CH2)n−OH、F(CF2)o(CH2)p−OH、F(CF2)qCH=CHCH2OH及びF(CF2)rCH2CH(I)CH2OHで示される化合物が挙げられる。尚、上記の式において、m、n、o、p、q及びrはそれぞれ独立に1〜8の整数を表す。 Specific examples of the fluorinated alcohol include H (CF 2 ) m (CH 2 ) n —OH, F (CF 2 ) o (CH 2 ) p —OH, F (CF 2 ) q CH═CHCH 2 OH and F (CF 2) a compound represented by r CH 2 CH (I) CH 2 OH and the like. In the above formula, m, n, o, p, q and r each independently represent an integer of 1 to 8.

含フッ素エーテルの具体例としては、R21−O−R22で示される化合物が挙げられる。尚、上記の式において、R21及びR22はそれぞれ独立に炭素数1〜10の直鎖又は分枝のアルキル基であり、R21及びR22の少なくとも一方がフッ素原子を含む。 Specific examples of the fluorine-containing ether include compounds represented by R 21 —O—R 22 . In the above formula, R 21 and R 22 are each independently a linear or branched alkyl group having 1 to 10 carbon atoms, and at least one of R 21 and R 22 contains a fluorine atom.

含フッ素エーテルとしては、例えば、ハイドロフルオロアルキルエーテルが挙げられる。また、含フッ素エーテルの市販品としては、例えば、住友スリーエム(株)製の「HE−7100」(商品名)及び「HFE−7200」(商品名)が挙げられる。   Examples of the fluorinated ether include hydrofluoroalkyl ether. Moreover, as a commercial item of fluorine-containing ether, Sumitomo 3M Co., Ltd. product "HE-7100" (brand name) and "HFE-7200" (brand name) are mentioned, for example.

ハイドロフルオロカーボンの具体例としては、鎖状構造及び環状構造のハイドロフルオロカーボンが挙げられる。   Specific examples of the hydrofluorocarbon include a hydrofluorocarbon having a chain structure and a cyclic structure.

ハイドロフルオロカーボンの市販品としては、例えば、三井・デュポンフロロケミカル(株)製の「バートレルHFC43−10mee」(商品名)及び日本ゼオン(株)製の「ゼオローラH」(商品名)が挙げられる。   Examples of commercially available hydrofluorocarbons include “Bertrel HFC43-10mee” (trade name) manufactured by Mitsui DuPont Fluorochemical Co., Ltd. and “Zeorolla H” (trade name) manufactured by Nippon Zeon Co., Ltd.

ジトリフルオロメチルベンゼンの具体例としては、o−ジトリフルオロメチルベンゼン、m−ジトリフルオロメチルベンゼン、p−ジトリフルオロメチルベンゼン及びこれらの混合物が挙げられる。   Specific examples of ditrifluoromethylbenzene include o-ditrifluoromethylbenzene, m-ditrifluoromethylbenzene, p-ditrifluoromethylbenzene, and mixtures thereof.

有機溶剤(b4)は1種又は2種以上を組み合わせて使用することができる。有機溶剤としては、硬化被膜(A)との密着性を向上させ、かつ、硬化被膜(B)の外観を良好とする点で、エタノール、2−プロパノール、酢酸エチル、トルエンが好ましく、酢酸エチルが特に好ましい。   The organic solvent (b4) can be used alone or in combination of two or more. As the organic solvent, ethanol, 2-propanol, ethyl acetate, and toluene are preferable, and ethyl acetate is preferable in terms of improving the adhesion with the cured film (A) and improving the appearance of the cured film (B). Particularly preferred.

<硬化被膜(B´)の形成方法>
硬化被膜(B´)の形成方法としては、例えば、硬化性組成物(s1)を硬化被膜(A)の表面に塗布した後に、硬化性組成物(s1)の塗膜を加熱又は活性エネルギー線を照射することにより、硬化性組成物(s1)を硬化させて、硬化被膜(B)を形成する方法が挙げられる。
<Method for forming cured coating (B ')>
As a method for forming the cured coating (B ′), for example, after applying the curable composition (s1) to the surface of the cured coating (A), the coating of the curable composition (s1) is heated or activated energy rays. Is a method of curing the curable composition (s1) to form a cured coating (B).

硬化被膜(A)の表面への硬化性組成物(s1)の塗布方法としては、硬化被膜(A)を形成する前記硬化性組成物の塗布方法と同様の方法が挙げられる。   Examples of the method for applying the curable composition (s1) to the surface of the cured film (A) include the same method as the method for applying the curable composition for forming the cured film (A).

<硬化被膜(B´)>
硬化被膜(B´)は、低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層から選ばれる1つの機能を有する層からなる機能層である。
<Hardened film (B ')>
The cured coating (B ′) is a functional layer composed of a layer having one function selected from a low refractive index layer, a high refractive index layer, a hard coat layer, an antistatic layer, an antiglare layer and an antifouling layer.

前記低屈折率層とは、屈折率が1.3〜1.5である層のことをいう。低屈折率化のために、前記硬化性組成物(s1)には必要に応じてコロイダルシリカを含有させることができる。コロイダルシリカとしては、多孔質シリカ及び非多孔質シリカから選ばれる少なくとも1種の微粒子を分散媒に分散させてコロイド溶液としたものを使用することができる。ここで、多孔質シリカは粒子内が多孔性又は中空であり、内部に空気を含有した低密度のシリカである。多孔質シリカの屈折率としては1.20〜1.40のものが挙げられ、通常のシリカの屈折率1.45〜1.47に比較して低い。また、本発明においては、必要に応じて、表面がシランカップリング剤処理されたコロイダルシリカを用いることができる。   The low refractive index layer refers to a layer having a refractive index of 1.3 to 1.5. In order to lower the refractive index, the curable composition (s1) may contain colloidal silica as necessary. As the colloidal silica, a colloidal solution obtained by dispersing at least one kind of fine particles selected from porous silica and non-porous silica in a dispersion medium can be used. Here, the porous silica is low-density silica in which the inside of the particle is porous or hollow and contains air inside. Examples of the refractive index of porous silica include 1.20 to 1.40, which is lower than the refractive index of 1.45 to 1.47 of ordinary silica. Moreover, in this invention, the colloidal silica by which the surface was processed with the silane coupling agent can be used as needed.

前記高屈折率層とは、屈折率が1.3〜1.5である層のことをいう。。高屈折率化のために、硬化性組成物(s1)には高屈折率の金属酸化物微粒子を分散させることができる。金属酸化物微粒子としては、例えば、金属アルコキシドを加水分解した後に縮合させて得られる金属酸化物が挙げられる。   The high refractive index layer refers to a layer having a refractive index of 1.3 to 1.5. . In order to increase the refractive index, metal oxide fine particles having a high refractive index can be dispersed in the curable composition (s1). Examples of the metal oxide fine particles include metal oxides obtained by condensing metal alkoxide after hydrolysis.

金属アルコキシドとしては、下式(II)で示されるものが挙げられる。

M(OR)m (II)
(式(II)中、Mは金属原子を表し、Rは炭素数1〜5の炭化水素基を表し、mは金属原子Mの原子価(3又は4)を表す。)
Examples of the metal alkoxide include those represented by the following formula (II).

M (OR) m (II)
(In formula (II), M represents a metal atom, R represents a hydrocarbon group having 1 to 5 carbon atoms, and m represents the valence (3 or 4) of the metal atom M.)

金属原子Mとしては、高屈折率層の屈折率の点で、チタン、アルミニウム、ジルコニウム及びスズが好ましく、チタンがより好ましい。   As the metal atom M, titanium, aluminum, zirconium and tin are preferable, and titanium is more preferable in view of the refractive index of the high refractive index layer.

金属アルコキシドの具体例としては、チタンメトキサイド、チタンエトキサイド、チタンn−プロポキサイド、チタンイソプロポキサイド、チタンn−ブトキサイド、チタンイソブトキサイド、アルミニウムエトキサイド、アルミニウムイソプロポキシド、アルミニウムブトキシド、アルミニウムt−ブトキサイド、スズt−ブトキサイド、ジルコニウムエトキサイド、ジルコニウムn−プロポキサイド、ジルコニウムイソプロポキサイド及びジルコニウムn−ブトキサイドが挙げられる。   Specific examples of the metal alkoxide include titanium methoxide, titanium ethoxide, titanium n-propoxide, titanium isopropoxide, titanium n-butoxide, titanium isobutoxide, aluminum ethoxide, aluminum isopropoxide, aluminum butoxide and aluminum. Examples include t-butoxide, tin t-butoxide, zirconium ethoxide, zirconium n-propoxide, zirconium isopropoxide and zirconium n-butoxide.

本発明においては、上記の金属酸化物膜の更なる高屈折率化を達成する観点から、上記の金属酸化物膜中に、高屈折率の金属酸化物であるZrO2、TiO2、NbO、ITO、ATO、SbO2、In2O3、SnO2及びZnOから選ばれる少なくとも1種の微粒子を分散させたものが好ましい。 In the present invention, from the viewpoint of achieving a higher refractive index of the metal oxide film, a high refractive index metal oxide, ZrO 2 , TiO 2 , NbO, ITO, ATO, SbO 2, in 2 O 3, those obtained by dispersing at least one kind of fine particles selected from SnO 2 and ZnO are preferable.

低屈折率層及び高屈折率層の膜厚の下限は、それぞれ50nm以上が好ましく、70nm以上がより好ましい。また、低屈折率層及び高屈折率層の膜厚の上限は、それぞれ200nm以下が好ましく、150nm以下がより好ましい。低屈折率層及び高屈折率層の膜厚は、それぞれ50nm以上200nm以下が好ましく、70nm以上150nm以下がより好ましい。膜厚がこの範囲であれば、視認される波長の反射光を十分抑制できる傾向にある。   The lower limit of the film thickness of the low refractive index layer and the high refractive index layer is preferably 50 nm or more, and more preferably 70 nm or more. Moreover, the upper limit of the film thickness of the low refractive index layer and the high refractive index layer is preferably 200 nm or less, and more preferably 150 nm or less. The film thicknesses of the low refractive index layer and the high refractive index layer are each preferably 50 nm to 200 nm, and more preferably 70 nm to 150 nm. When the film thickness is within this range, reflected light having a visible wavelength tends to be sufficiently suppressed.

前記反射防止層としては、例えば、硬化被膜(A)より低い屈折率を有する低屈折率層、高屈折率層の上に低屈折率層が積層された2層構造を有する積層構造又は高屈折率層の上に中屈折率層及び低屈折率層が順次積層された3層構造を有する積層構造のものが挙げられる。反射防止層としては、樹脂積層体の表面において樹脂積層体の内部に向かう方向に入射した光の反射光の光量が入射光の光量の0%以上20%以下となるものが好ましく、0%以上10%以下となるものがより好ましく、0%以上5%以下となるものがさらに好ましい。   Examples of the antireflection layer include a low refractive index layer having a refractive index lower than that of the cured coating (A), a laminated structure having a two-layer structure in which a low refractive index layer is laminated on a high refractive index layer, or a high refractive index. A layered structure having a three-layer structure in which a middle refractive index layer and a low refractive index layer are sequentially laminated on the refractive index layer can be mentioned. The antireflection layer is preferably such that the amount of reflected light of light incident in the direction toward the inside of the resin laminate on the surface of the resin laminate is 0% or more and 20% or less of the amount of incident light. What becomes 10% or less is more preferable, and what becomes 0% or more and 5% or less is still more preferable.

反射防止層が、高屈折率層の上に低屈折率層が積層された2層構造を有する場合には、例えば、前記低屈折率層の屈折率は1.3〜1.5、高屈折率層の屈折率は1.6〜2.0の範囲であることが好ましい。この範囲であれば、入射光の反射を十分抑制できる。   When the antireflection layer has a two-layer structure in which a low refractive index layer is laminated on a high refractive index layer, for example, the refractive index of the low refractive index layer is 1.3 to 1.5, and a high refractive index The refractive index of the refractive index layer is preferably in the range of 1.6 to 2.0. If it is this range, reflection of incident light can be sufficiently suppressed.

硬化被膜(B´)を帯電防止層とする場合、硬化性組成物(s1)へ、公知の帯電防止成分を添加すれば良い。帯電防止成分は、電子伝導型の有機化合物や導電性粒子、イオン伝導型の有機化合物などが挙げられる。   When the cured coating (B ′) is used as an antistatic layer, a known antistatic component may be added to the curable composition (s1). Examples of the antistatic component include an electron conductive organic compound, conductive particles, and an ion conductive organic compound.

π共役系導電性有機化合物としては、脂肪族共役系のポリアセチレン、芳香族共役系のポリ(パラフェニレン)、複素環式共役系のポリピロール等が挙げられる。   Examples of the π-conjugated conductive organic compound include aliphatic conjugated polyacetylene, aromatic conjugated poly (paraphenylene), and heterocyclic conjugated polypyrrole.

導電性微粒子としては、カーボン系、金属酸化物系、導電被覆系微粒子等が挙げられる。   Examples of the conductive fine particles include carbon-based, metal oxide-based, and conductive coating-based fine particles.

カーボン系微粒子としては、カーボンブラック、ケッチェンブラック、アセチレンブラック等のカーボン粉末、PAN系炭素繊維、ピッチ系炭素繊維等のカーボン繊維等が挙げられる。   Examples of the carbon-based fine particles include carbon powders such as carbon black, ketjen black, and acetylene black, and carbon fibers such as PAN-based carbon fibers and pitch-based carbon fibers.

金属酸化物系微粒子としては、酸化錫、アンチモンをドープした酸化錫(ATO)、酸化インジウム、スズをドープした酸化インジウム(ITO)、酸化亜鉛、アルミニウムをドープした酸化亜鉛、アンチモン酸亜鉛、五酸化アンチモンなどが挙げられる。   Metal oxide fine particles include tin oxide, antimony-doped tin oxide (ATO), indium oxide, tin-doped indium oxide (ITO), zinc oxide, aluminum-doped zinc oxide, zinc antimonate, pentoxide And antimony.

導電被覆系微粒子としては、例えば、酸化チタン(球状、針状)、チタン酸カリウム、硫酸バリウム、マイカ、シリカ等の各種微粒子表面を、酸化錫、ATO、ITO等の帯電防止成分で被覆した導電性微粒子、金及び/またはニッケルなどの金属で表面処理されたポリスチレン、アクリル樹脂、エポキシ樹脂、ポリアミド樹脂、ポリウレタン樹脂等の樹脂ビーズが好ましい。 イオン伝導型の有機化合物としては、四級アンモニウム塩基を有する化合物、ポリスチレンスルホン酸等が挙げられる。   Examples of the conductive coated fine particles include conductive particles in which various fine particle surfaces such as titanium oxide (spherical, needle-shaped), potassium titanate, barium sulfate, mica, silica, etc. are coated with antistatic components such as tin oxide, ATO, and ITO. Resin beads such as polystyrene, acrylic resin, epoxy resin, polyamide resin, and polyurethane resin, which are surface-treated with a metal such as conductive fine particles, gold and / or nickel, are preferable. Examples of the ion conductive organic compound include compounds having a quaternary ammonium base, polystyrene sulfonic acid, and the like.

前記防眩層としては、硬化被膜(B´)を防眩層とする場合、防眩層の表面に微細凹凸を形成する方法及び防弦層の内部に光拡散性微粒子を添加して内部散乱により外光を乱反射させる方法の少なくとも1つの方法により外光の映りこみを抑制することができる。光拡散性微粒子としては、有機微粒子又は無機微粒子を使用することができる。有機微粒子としては、例えば、アクリル樹脂(PMMA)、ポリスチレン(PS)、アクリル−スチレン共重合体、メラミン樹脂、ポリカーボート(PC)等を用いることができる。有機微粒子は、架橋や未架橋等の特性には特に限定されるものではなく、任意に選択できる。また、無機微粒子としては、例えば、酸化珪素、酸化チタン、酸化アルミニウム、酸化亜鉛、酸化錫、炭酸カルシウム、硫酸バリウム、タルク、カオリン及び硫酸カルシウムが挙げられる。これらの無機微粒子に対して例えばシランカップリング処理等の有機物処理を施すことにより、該微粒子が有機物に分散し易くすることが好ましい。   As the antiglare layer, when the cured coating (B ′) is an antiglare layer, a method for forming fine irregularities on the surface of the antiglare layer, and light scattering particles are added to the inside of the string prevention layer to cause internal scattering. Thus, reflection of external light can be suppressed by at least one method of irregularly reflecting external light. As the light diffusing fine particles, organic fine particles or inorganic fine particles can be used. As the organic fine particles, for example, acrylic resin (PMMA), polystyrene (PS), acrylic-styrene copolymer, melamine resin, polycarbonate (PC) and the like can be used. The organic fine particles are not particularly limited in properties such as crosslinking and non-crosslinking, and can be arbitrarily selected. Examples of the inorganic fine particles include silicon oxide, titanium oxide, aluminum oxide, zinc oxide, tin oxide, calcium carbonate, barium sulfate, talc, kaolin and calcium sulfate. These inorganic fine particles are preferably subjected to an organic treatment such as a silane coupling treatment so that the fine particles are easily dispersed in the organic matter.

前記無機微粒子の大きさは、適宜選択することができる。樹脂積層体表面の微細凹凸の形状としては、表面中心線平均粗さが0.05μm以上0.3μm以下、微細凹凸のピッチが30μm以上200μm以下であることが好ましく、このようになる粒子径の微粒子を用いることになる。   The size of the inorganic fine particles can be appropriately selected. As the shape of the fine irregularities on the surface of the resin laminate, the surface center line average roughness is preferably 0.05 μm or more and 0.3 μm or less, and the pitch of the fine irregularities is preferably 30 μm or more and 200 μm or less. Fine particles will be used.

前記防汚層としては、撥水性又は撥油性を有すること、若しくは、親水性又は親油性を有することが好ましい。指紋、皮脂、汗、化粧品等の汚れが付着した際、汚れを除去し易い観点から撥水性と撥油性を有することが好ましい。防汚層に撥水性と撥油性を付与する方法としては、前記硬化性組成物(s1)に、フッ素原子を有する(メタ)アクリレート単量体を添加する方法が挙げられる。前記フッ素原子を有する(メタ)アクリレート単量体は特に限定されるものではなく、公知の化合物を使用できる。   The antifouling layer preferably has water repellency or oil repellency, or has hydrophilicity or lipophilicity. When dirt such as fingerprints, sebum, sweat, cosmetics, etc. adheres, it is preferable to have water repellency and oil repellency from the viewpoint of easily removing the dirt. Examples of a method for imparting water repellency and oil repellency to the antifouling layer include a method of adding a (meth) acrylate monomer having a fluorine atom to the curable composition (s1). The (meth) acrylate monomer having a fluorine atom is not particularly limited, and a known compound can be used.

具体的には、へプタデカンフルオロデシルアクリレートである「ビスコート17F」(商品名、大阪有機化学工業(株)製)、パーフルオロオクチルエチルアクリレートである「ライトアクリレートFA−108」(商品名、共栄社化学(株)製)、1,10−ビス(メタ)アクリロイルオキシ−2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9−ヘキサデカフルオロデカンである「16−FDA」(商品名、共栄社化学(株)製)が挙げられる。撥水層の撥水性能又は撥油性能を良好とする場合には、パーフルオロポリエーテル基を有する(メタ)アクリレートが好ましい。具体的には、ダイキン工業(株)製「オプツールDAC」(商品名)、DIC(株)製「EXP RS−503」及び「EXP RS−751−k」が挙げられる。   Specifically, “Biscoat 17F” (trade name, manufactured by Osaka Organic Chemical Industry Co., Ltd.), which is heptadecane fluorodecyl acrylate, “Light acrylate FA-108” (trade name, Kyoeisha), which is perfluorooctylethyl acrylate. Chemical Co., Ltd.), 1,10-bis (meth) acryloyloxy-2,2,3,3,4,4,5,5,6,6,7,7,8,8,9,9- “16-FDA” (trade name, manufactured by Kyoeisha Chemical Co., Ltd.), which is hexadecafluorodecane. In order to improve the water repellency or oil repellency of the water repellent layer, a (meth) acrylate having a perfluoropolyether group is preferred. Specific examples include “OPTOOL DAC” (trade name) manufactured by Daikin Industries, Ltd., “EXP RS-503” and “EXP RS-751-k” manufactured by DIC Corporation.

フッ素原子を有する(メタ)アクリレート単量体は1種または2種以上を組み合わせて使用することができる。 <硬化被膜(B´)>
硬化被膜(B´´)は、硬化被膜(A)と後述する機能層(C)を接着させる接着層である。
The (meth) acrylate monomer which has a fluorine atom can be used 1 type or in combination of 2 or more types. <Hardened film (B ')>
The cured film (B ″) is an adhesive layer that adheres the cured film (A) and a functional layer (C) described later.

<硬化被膜(B´´)の形成方法>
硬化被膜(B´´)の形成方法の好ましい例として、以下の方法が挙げられる。
<Method for forming cured coating (B ″)>
The following method is mentioned as a preferable example of the formation method of a cured film (B '').

後述する機能層(C)を形成した樹脂フィルム表面の機能層(C)と、硬化被膜(A)を積層した樹脂積層体とを、硬化性組成物(s2)を介してラミネートする。この硬化性組成物(s2)は、ロールコート、バーコート、スリットダイなどを用いて塗布することにより塗布層を形成することができる。   A functional layer (C) on the surface of the resin film on which a functional layer (C) described later is formed and a resin laminate on which the cured coating (A) is laminated are laminated via the curable composition (s2). This curable composition (s2) can form a coating layer by coating using a roll coat, a bar coat, a slit die or the like.

樹脂フィルム表面に後述する機能層(C)を形成し、さらに該機能層(C)の表面にロールコート、バーコート、スリットダイなどを用いて塗布することにより塗布層を形成する。   A functional layer (C), which will be described later, is formed on the surface of the resin film, and further, a coating layer is formed on the surface of the functional layer (C) by using a roll coat, a bar coat, a slit die or the like.

前記塗布層が形成された機能層(C)を形成した樹脂フィルム表面を樹脂基材に貼り付ける方法としては、ゴムロールで圧着する方法が挙げられる。この際、樹脂基材の表面温度を40℃〜100℃とすることが好ましい。かかる範囲の温度では、密着性を良好にでき、基材の過度の溶解による硬度低下を抑えることができ、塗膜の黄変を低減できる。樹脂基材の表面温度は、加熱部の設定温度、加熱時間等により調整することができる。樹脂基材の温度の測定方法としては、非接触型表面温度計等、公知の方法が挙げられる。   Examples of a method for attaching the resin film surface on which the functional layer (C) on which the coating layer has been formed to the resin base material include a method of pressure bonding with a rubber roll. At this time, the surface temperature of the resin base material is preferably set to 40 ° C to 100 ° C. When the temperature is within such a range, the adhesion can be improved, a decrease in hardness due to excessive dissolution of the substrate can be suppressed, and yellowing of the coating film can be reduced. The surface temperature of the resin substrate can be adjusted by the set temperature of the heating unit, the heating time, and the like. As a method for measuring the temperature of the resin substrate, a known method such as a non-contact type surface thermometer can be used.

転写フィルムを介して活性エネルギー線を照射し、硬化性組成物(s2)を硬化させて硬化被膜(B´´)とする。活性エネルギー線としては、紫外線が好ましい。前記樹脂フィルムを剥離し、硬化被膜(A)の上に硬化被膜(B´´)、機能層(C)を順次積層した樹脂積層体を得ることができる。   The active energy ray is irradiated through the transfer film to cure the curable composition (s2) to form a cured coating (B ″). As the active energy ray, ultraviolet rays are preferable. The resin film is peeled, and a resin laminate in which a cured coating (B ″) and a functional layer (C) are sequentially laminated on the cured coating (A) can be obtained.

<機能層(C)>
機能層(C)は、本発明の樹脂積層体を構成する構成要素の1つであり、前記硬化被膜(A)の第1面に形成された硬化被膜(B)の表面に形成されるものである。
<Functional layer (C)>
The functional layer (C) is one of the components constituting the resin laminate of the present invention, and is formed on the surface of the cured film (B) formed on the first surface of the cured film (A). It is.

機能層(C)は、低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層から選ばれる1つの機能を有する機能層であり、上述した硬化被膜(B´)に記載した硬化被膜を用いることができる。   The functional layer (C) is a functional layer having one function selected from a low refractive index layer, a high refractive index layer, a hard coat layer, an antistatic layer, an antiglare layer, and an antifouling layer. The cured coating described in B ′) can be used.

前記機能層(C)の膜厚は、特に制限されるものではないが、0.05μm以上5.0μm以下が好ましい。機能層(C)の膜厚の下限は、樹脂積層体の外観が良好となる観点から0.05μm以上が好ましい。また、機能層(C)の膜厚の上限は、硬化被膜(B)と機能層(C)の密着性が向上する観点から5.0μm以下が好ましい。機能層(C)の膜厚の下限は0.1μm以上がより好ましく、膜厚の上限は3.0μm以下がより好ましい。即ち、機能層(C)の膜厚は、0.1μm以上3.0μm以下がより好ましい。   The film thickness of the functional layer (C) is not particularly limited, but is preferably 0.05 μm or more and 5.0 μm or less. The lower limit of the film thickness of the functional layer (C) is preferably 0.05 μm or more from the viewpoint of improving the appearance of the resin laminate. Moreover, the upper limit of the film thickness of the functional layer (C) is preferably 5.0 μm or less from the viewpoint of improving the adhesion between the cured film (B) and the functional layer (C). The lower limit of the film thickness of the functional layer (C) is more preferably 0.1 μm or more, and the upper limit of the film thickness is more preferably 3.0 μm or less. That is, the thickness of the functional layer (C) is more preferably 0.1 μm or more and 3.0 μm or less.

<機能層(C)の形成方法>
機能層(C)の形成方法は、後述する樹脂フィルムの表面に機能層(C)を一旦転写層として形成したあと、前記硬化被膜(A)の第1面に接着層として設けられた硬化被膜(B)の表面に転写され、樹脂積層体を形成する方法が挙げられる。
<Method for forming functional layer (C)>
The functional layer (C) is formed by forming a functional layer (C) as a transfer layer once on the surface of a resin film, which will be described later, and then providing a cured film provided as an adhesive layer on the first surface of the cured film (A). The method of transferring to the surface of (B) and forming a resin laminated body is mentioned.

機能層(C)を樹脂フィルムの表面に転写層として形成する具体的な方法としては、前記硬化性組成物(s1)に各機能層を形成する成分を添加した後、該硬化性組成物(s1)を樹脂フィルムの表面に塗布し、次いで該硬化性組成物(s1)の塗膜を、加熱又は活性エネルギー線を照射することにより硬化させて、機能層(C)を形成する方法が挙げられる。   As a specific method for forming the functional layer (C) as a transfer layer on the surface of the resin film, after adding the components for forming each functional layer to the curable composition (s1), the curable composition ( A method of forming the functional layer (C) by applying s1) to the surface of the resin film and then curing the coating film of the curable composition (s1) by heating or irradiating active energy rays. It is done.

樹脂フィルムの表面に硬化性組成物(s1)を塗布する方法としては、上述した硬化被膜(A)を形成する硬化性組成物の塗布方法に記載した方法が挙げられる。   Examples of the method for applying the curable composition (s1) to the surface of the resin film include the methods described in the method for applying the curable composition for forming the cured film (A) described above.

<樹脂フィルム>
硬化被膜(B)の製造に用いられる樹脂フィルムとしては、例えば、活性エネルギー線透過性及び耐溶剤性に優れ、酸素透過性の低いものが挙げられる。
<Resin film>
As a resin film used for manufacture of a cured film (B), what is excellent in active energy ray permeability | transmittance and solvent resistance, and a low oxygen permeability is mentioned, for example.

樹脂フィルムの具体例としては、ポリエチレンテレフタレートフィルム(以下、「PETフィルム」という);ナイロンフィルム;ポリカーボネートフィルム;アクリル系フィルム;ポリプロピレン、ポリエチレン等のポリオレフィン系フィルム;ジアセチルセルロース、トリアセチルセルロース等のセルロース系フィルム及びポリ塩化ビニリデン系フィルムが挙げられる。これらの中で、透明性及び耐溶剤性を有し、酸素の透過率が低い点でPETフィルムが好ましい。   Specific examples of the resin film include polyethylene terephthalate film (hereinafter referred to as “PET film”); nylon film; polycarbonate film; acrylic film; polyolefin film such as polypropylene and polyethylene; and cellulose film such as diacetyl cellulose and triacetyl cellulose. Examples thereof include a film and a polyvinylidene chloride film. Among these, a PET film is preferable because it has transparency and solvent resistance and has a low oxygen permeability.

また、離型処理層が形成されている市販のフィルムを使用することができる。   Moreover, the commercially available film in which the mold release process layer is formed can be used.

樹脂フィルムの厚みは特に制限されるものではないが、5.0μm以上300μm以下が好ましく、10μm以上200μm以下がより好ましい。樹脂フィルムの厚みの下限が5.0μm以上であれば、フィルムのうねりやたわみによる硬化被膜の外観低下を抑制できる。また、樹脂フィルムの厚みの上限が200μm以下であれば、機能層(C)の膜厚の調整が容易になる。   The thickness of the resin film is not particularly limited, but is preferably 5.0 μm or more and 300 μm or less, and more preferably 10 μm or more and 200 μm or less. If the minimum of the thickness of a resin film is 5.0 micrometers or more, the external appearance fall of the cured film by the wave | undulation and bending of a film can be suppressed. Moreover, if the upper limit of the thickness of a resin film is 200 micrometers or less, adjustment of the film thickness of a functional layer (C) will become easy.

<樹脂積層体の製造方法>
本発明の樹脂積層体を製造する一実施態様としては、例えば、下記工程(1)及び工程(2)を含む方法が挙げられる。
<Method for producing resin laminate>
As one embodiment which manufactures the resin laminated body of this invention, the method containing the following process (1) and process (2) is mentioned, for example.

工程(1):樹脂基材の少なくとも一方の表面に、分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(a1)、分子中に2個以下の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(a2)を含む硬化被膜(A)を形成する。 Step (1): A repeating unit (a1) derived from a monomer having 3 or more (meth) acryloyloxy groups in the molecule on at least one surface of the resin substrate, and 2 or less (meta ) A cured coating (A) containing a repeating unit (a2) derived from a monomer having an acryloyloxy group is formed.

工程(2):前記硬化被膜(A)の表面に、ウレタン(メタ)アクリレート由来の繰り返し単位(b2−1)及びアミノ基を有するメタクリレート由来の繰り返し単位(b2−2)の少なくとも1種類を含む硬化被膜(B)を形成する。 Step (2): The surface of the cured film (A) contains at least one of a repeating unit (b2-1) derived from urethane (meth) acrylate and a repeating unit (b2-2) derived from a methacrylate having an amino group. A cured coating (B) is formed.

上記の工程(1)としては、例えば、樹脂基材の少なくとも一方の表面に、前記(a1)成分及び前記(a2)成分を含む硬化性樹脂組成物の塗膜を形成をした後、硬化して、樹脂基材の少なくとも一方の表面に硬化被膜(A)が形成された積層樹脂体を形成する方法が挙げられる。   As said process (1), after forming the coating film of the curable resin composition containing the said (a1) component and the said (a2) component on at least one surface of a resin base material, it hardens | cures, for example. And a method of forming a laminated resin body in which the cured coating (A) is formed on at least one surface of the resin base material.

前記工程(1)における、硬化被膜(A)の鉛筆硬度は8H以上であることが好ましい。硬化被膜(A)の表面の鉛筆硬度を8H以上とすることにより、指の爪等による引掻き傷が樹脂積層体の表面に発生することを抑制できるので、耐擦傷性の良好な樹脂積層体を得ることができる。   In the step (1), the cured film (A) preferably has a pencil hardness of 8H or more. By setting the pencil hardness of the surface of the cured coating (A) to 8H or more, it is possible to suppress the occurrence of scratches caused by fingernails on the surface of the resin laminate, so that a resin laminate having good scratch resistance can be obtained. Can be obtained.

前記工程(2)において硬化被膜(B)を形成する処理は、下記の工程(2−1)〜(2−3)を含むことができる。   The process for forming the cured coating (B) in the step (2) can include the following steps (2-1) to (2-3).

工程(2−1):工程(1)の硬化被膜(A)の表面に、分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体(b1)、ウレタン(メタ)アクリレート単量体(b2−1)及びアミノ基を有する(メタ)アクリレート単量体(b2−2)の少なくとも1種類(ただし、単量体(b1)を除く)、有機溶剤(b4)を含む硬化性組成物(s1)の塗膜を形成する。 Step (2-1): Monomer (b1) having three or more (meth) acryloyloxy groups in the molecule on the surface of the cured film (A) in step (1), urethane (meth) acrylate monomer A curable composition comprising at least one of (b2-1) and (meth) acrylate monomer (b2-2) having an amino group (excluding monomer (b1)) and organic solvent (b4) A coating film of the object (s1) is formed.

工程(2−2):前記硬化性組成物(s1)の塗膜を乾燥する。 Step (2-2): The coating film of the curable composition (s1) is dried.

工程(2−3):前記乾燥後の硬化性組成物(s1)の塗膜を硬化して、硬化被膜(B)を形成する。 Step (2-3): The coating film of the curable composition (s1) after drying is cured to form a cured film (B).

工程(2−1)の硬化性組成物の塗膜を形成する方法としては、例えば、流延法、ローラーコート法、バーコート法、噴霧コート法、エアーナイフコート法、スピンコート法、フローコート法、カーテンコート法、フィルムカバー法及びディッピング法が挙げられる。   Examples of the method for forming a coating film of the curable composition in the step (2-1) include a casting method, a roller coating method, a bar coating method, a spray coating method, an air knife coating method, a spin coating method, and a flow coating. Method, curtain coating method, film cover method and dipping method.

硬化性樹脂組成物の塗膜を硬化する方法としては、塗膜を加熱する方法又は上述したように塗膜に活性エネルギー線を照射する方法が挙げられる。   Examples of the method of curing the coating film of the curable resin composition include a method of heating the coating film or a method of irradiating the coating film with active energy rays as described above.

工程(2−2)乾燥する方法、工程(2−3)の加熱する方法としては、例えば、空気雰囲気下で、遠赤外線ヒーター等の熱源を用いて90〜150℃の条件で熱処理する方法が挙げられる。また、積層鋳型中の樹脂積層体を構成する樹脂組成物の重合率を高めるために、必要に応じて積層鋳型を30〜98℃の温水等の熱源で加熱することができる。また、熱処理後に、必要に応じて送風等の冷却処理を行うことができる。   As a method of drying in step (2-2) and a method of heating in step (2-3), for example, a method of heat treatment under a condition of 90 to 150 ° C. using a heat source such as a far infrared heater in an air atmosphere. Can be mentioned. Moreover, in order to raise the polymerization rate of the resin composition which comprises the resin laminated body in a lamination mold, a lamination mold can be heated with heat sources, such as 30-98 ° C warm water, as needed. Further, after the heat treatment, a cooling treatment such as blowing can be performed as necessary.

また、本発明の樹脂積層体を製造する、別の一実施態様としては、前記工程(2)の硬化被膜(B)を形成する工程が、前記硬化被膜(A)の表面に、分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体(b1)、ウレタン(メタ)アクリレート単量体(b2−1)及びアミノ基を有する(メタ)アクリレート単量体(b2−2)の少なくとも1種類(ただし、単量体(b1)を除く)を含む硬化性組成物(s2)の塗膜を形成し、硬化して、硬化被膜(B´´)を形成することを含み、さらに工程(2)の後に、下記工程(3)〜(5)を行うことを含む方法が挙げられる。。   Moreover, as another embodiment which manufactures the resin laminated body of this invention, the process of forming the cured film (B) of the said process (2) is carried out in the molecule | numerator on the surface of the said cured film (A). Of a monomer (b1) having three or more (meth) acryloyloxy groups, a urethane (meth) acrylate monomer (b2-1), and a (meth) acrylate monomer (b2-2) having an amino group Forming a cured film of the curable composition (s2) containing at least one type (excluding the monomer (b1)) and curing to form a cured film (B ″); The method including performing following process (3)-(5) after process (2) is mentioned. .

工程(3):樹脂フィルムの表面に、低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層から選ばれる少なくとも1つの機能を有する層からなる、機能層(C)を形成する。 Step (3): a function comprising a layer having at least one function selected from a low refractive index layer, a high refractive index layer, a hard coat layer, an antistatic layer, an antiglare layer and an antifouling layer on the surface of the resin film Layer (C) is formed.

工程(4):前記工程(2)で得られた硬化被膜(B´´)の表面に、前記工程(3)の機能層(C)を貼り合わせる。 Step (4): The functional layer (C) of the step (3) is bonded to the surface of the cured film (B ″) obtained in the step (2).

工程(5):前記樹脂フィルムを剥離し、樹脂基材の少なくとも一方の表面に、硬化被膜(A)硬化被膜(B´´)、機能層(C)が順次積層された樹脂積層体を得る。 Step (5): The resin film is peeled off to obtain a resin laminate in which the cured coating (A), the cured coating (B ″), and the functional layer (C) are sequentially laminated on at least one surface of the resin base material. .

工程(5)において、樹脂フィルムの表面に機能層(C)として反射防止層や防眩層を形成させる場合の具体例を以下に示す。 反射防止層の形成方法としては、例えば、流延法、ローラーコート法、バーコート法、噴霧コート法、エアーナイフコート法、スピンコート法、フローコート法、カーテンコート法、フィルムカバー法及びディッピング法が挙げられる。   In the step (5), specific examples in the case of forming an antireflection layer or an antiglare layer as the functional layer (C) on the surface of the resin film are shown below. Examples of the method for forming the antireflection layer include a casting method, a roller coating method, a bar coating method, a spray coating method, an air knife coating method, a spin coating method, a flow coating method, a curtain coating method, a film cover method, and a dipping method. Is mentioned.

防眩層の形成方法としては、例えば、樹脂フィルムの表面に防眩層を積層する場合、防眩層の表面に微細凹凸を形成する方法、及び防弦層中に光拡散性微粒子を添加して内部散乱により外光を乱反射させる方法の少なくとも1つの方法により外光の映りこみを抑制することができる。具体的には、以下の2とおりの方法が挙げられる。   As a method for forming an antiglare layer, for example, when laminating an antiglare layer on the surface of a resin film, a method of forming fine irregularities on the surface of the antiglare layer, and adding light diffusing fine particles in the stringproof layer Thus, reflection of external light can be suppressed by at least one method of irregularly reflecting external light by internal scattering. Specifically, there are the following two methods.

第1の方法においては、活性エネルギー線透過性フィルムの表面に公知の方法で微細凹凸形状を形成した後、微細凹凸形状が形成された面に、防眩層形成用組成物の塗膜を形成した後に、硬化させ、防眩層が積層された活性エネルギー線透過性フィルムを得る。その後、前記工程(4)で得られた硬化性組成物(s2)の塗膜の表面に、上記の防眩層が積層された活性エネルギー線透過性フィルムの防眩層の面が接するように積層した後、活性エネルギー線透過性フィルムを剥離することにより、樹脂積層体の表面に微細凹凸形状の表面を有する防眩層が積層された積層体を得る。   In the first method, after forming a fine uneven shape on the surface of the active energy ray transmissive film by a known method, a coating film of the composition for forming an antiglare layer is formed on the surface on which the fine uneven shape is formed. Then, it is cured to obtain an active energy ray transparent film on which an antiglare layer is laminated. Then, the surface of the antiglare layer of the active energy ray-transmitting film in which the antiglare layer is laminated is in contact with the surface of the coating film of the curable composition (s2) obtained in the step (4). After the lamination, the active energy ray-permeable film is peeled off to obtain a laminate in which an antiglare layer having a fine uneven surface is laminated on the surface of the resin laminate.

第2の方法は、活性エネルギー線透過性フィルムの表面自体に凹凸形状を持たせる方法であり、例えば、活性エネルギー線透過性フィルムを形成するための粒子を樹脂中に練りこむ方法や、或いはまた、活性エネルギー線透過性フィルムを形成するための樹脂をガラス転移温度以上に加熱した状態で微細凹凸形状を有する型と接触させて型の表面の微細凹凸形状を転写させる方法が挙げられる。   The second method is a method in which the surface of the active energy ray permeable film itself has an uneven shape, for example, a method of kneading particles for forming an active energy ray permeable film into a resin, or And a method for transferring the fine irregularities on the surface of the mold by bringing the resin for forming the active energy ray transmissive film into contact with a mold having fine irregularities in a state where the resin is heated to a glass transition temperature or higher.

前記工程(5)において機能層(C)の膜厚は、特に制限されるものではないが、樹脂積層体の外観が良好となること、樹脂積層体の全体の膜厚斑が抑制できること及び硬化被膜(B)と機能層(C)の密着性が向上する点から、0.05μm以上5.0μm以下が好ましい。   In the step (5), the thickness of the functional layer (C) is not particularly limited, but the appearance of the resin laminate can be improved, the uneven thickness of the resin laminate can be suppressed, and curing. From the viewpoint of improving the adhesion between the coating (B) and the functional layer (C), it is preferably 0.05 μm or more and 5.0 μm or less.

以下、実施例により本発明を詳しく説明する。尚、実施例における各種評価は下記の方法により実施した。   Hereinafter, the present invention will be described in detail by way of examples. In addition, various evaluation in an Example was implemented with the following method.

(1)硬化被膜の膜厚
樹脂積層体の厚み方向にミクロトームで幅100nmのサンプルを切り出し、透過型電子顕微鏡(日本電子(株)製JEM−1010(商品名))で樹脂積層体の断面を観察し、硬化被膜(A)、硬化被膜(B´)及び硬化被膜(B´´)の膜厚を測定した。
の膜厚を測定した。
(1) Film thickness of cured coating A sample having a width of 100 nm was cut out with a microtome in the thickness direction of the resin laminate, and a cross section of the resin laminate was observed with a transmission electron microscope (JEM-1010 (trade name) manufactured by JEOL Ltd.). The film thicknesses of the cured film (A), the cured film (B ′), and the cured film (B ″) were measured.
The film thickness of was measured.

(2)全光線透過率及びヘイズ値
HAZE METER(日本電色工業(株)製、商品名:NDH4000)を用いてISO 13468−1:1996に示される測定法に準拠して、樹脂積層体の全光線透過率を測定し、ISO 14782:1999に示される測定法に準拠して、樹脂積層体のヘイズ値を測定した。
(2) Total light transmittance and haze value
Based on the measurement method shown in ISO 13468-1: 1996 using HAZE METER (manufactured by Nippon Denshoku Industries Co., Ltd., trade name: NDH4000), the total light transmittance of the resin laminate is measured and ISO 14782 is obtained. : Based on the measurement method shown in 1999, the haze value of the resin laminate was measured.

(3)鉛筆硬度
樹脂積層体の表面硬度が、鉛筆硬度により評価した。硬化被膜(B)を積層する前の樹脂積層体、及び硬化被膜(B)を積層した後の樹脂積層体について、最表層の鉛筆硬度をISO 2409:1992に準拠して測定した。
(3) Pencil hardness The surface hardness of the resin laminate was evaluated by pencil hardness. About the resin laminated body before laminating | stacking a cured film (B), and the resin laminated body after laminating | stacking a cured film (B), the pencil hardness of the outermost layer was measured based on ISO2409: 1992.

(4)耐擦傷性
樹脂積層体の最表層の耐擦傷性は、擦傷試験後のサンプルの傷の本数より評価した。擦傷試験は、#000のスチールウール(日本スチールウール(株)製、商品名:ボンスターNo.000)を装着した直径24mmの円形パッドを樹脂積層体の最表層に置き、1,000gの荷重下で20mmの距離を、100回往復させて実施した。
(4) The scratch resistance of the outermost layer of the scratch-resistant resin laminate was evaluated from the number of scratches on the sample after the scratch test. In the abrasion test, a round pad with a diameter of 24 mm on which # 000 steel wool (manufactured by Nippon Steel Wool Co., Ltd., trade name: Bonster No. 000) was placed was placed on the outermost layer of the resin laminate, and the load was 1,000 g. The distance of 20 mm was reciprocated 100 times.

(5)耐クラック性
樹脂積層体の表面の耐クラック性を、樹脂積層体を曲率半径100mm、80mm、60mm及び40mmに曲げた時のクラック発生の有無を観察することにより評価した。耐クラック性の評価は、以下の手順で行った。幅30mm、長さ120mm及び厚み1mmの樹脂積層体を、半円筒形の型であって、断面の弧の曲率半径Rが100mm、80mm、60mm及び40mm、底辺の長さが100mmである木製の型の上に樹脂積層体の硬化被膜の最表層が鉛直方向上側になるように樹脂積層体を載置した。樹脂積層体の全体を型の弧に沿って曲げて、30秒間保持した。その後、樹脂積層体を目視観察し、クラックが発生しない最も小さい曲率半径を測定した。
(5) Crack resistance The crack resistance of the surface of the resin laminate was evaluated by observing the occurrence of cracks when the resin laminate was bent to a radius of curvature of 100 mm, 80 mm, 60 mm and 40 mm. Evaluation of crack resistance was performed according to the following procedure. A resin laminate having a width of 30 mm, a length of 120 mm and a thickness of 1 mm is a semi-cylindrical mold, and the cross-section arc radius of curvature R is 100 mm, 80 mm, 60 mm and 40 mm, and the base length is 100 mm. The resin laminate was placed on the mold so that the outermost layer of the cured film of the resin laminate was on the upper side in the vertical direction. The entire resin laminate was bent along the arc of the mold and held for 30 seconds. Thereafter, the resin laminate was visually observed, and the smallest radius of curvature at which no crack was generated was measured.

(6)硬化被膜の残存率
ISO 2409:1992に準拠してクロスカット剥離試験を実施した時の、樹脂積層体の表面に残存している硬化被膜(B)の残存率、又は硬化被膜(B)及び機能層(C)の残存率を評価した。
(6) Residual rate of cured coating When the cross-cut peel test is performed according to ISO 2409: 1992, the residual rate of the cured coating (B) remaining on the surface of the resin laminate, or the cured coating (B ) And the residual ratio of the functional layer (C).

(7)環境試験後の硬化被膜の残存率
樹脂積層体を温度60℃及び相対湿度95%の恒温恒湿機に100時間放置した後に取り出し、(6)の方法で硬化被膜(B)又は硬化被膜(B)及び機能層(C)の残存率を評価した。
(7) Residual rate of cured film after environmental test The resin laminate is left to stand for 100 hours in a constant temperature and humidity machine at a temperature of 60 ° C. and a relative humidity of 95%, and is taken out and cured film (B) or cured by the method of (6) The residual rate of the coating (B) and the functional layer (C) was evaluated.

以下において、略称は下記の単量体又は化合物を示す。
ポリアクリレート1:ジペンタエリスリトールヘキサアクリレート(60〜70質量%)とジペンタエリスリトールペンタアクリレート(40〜30質量%)の混合物。
ポリアクリレート2:ペンタエリスリトールトリアクリレート(50〜70質量%)とペンタエリスリトールテトラアクリレート(50〜30質量%)の混合物
ジアクリレート1:1,6−ヘキサンジオールジアクリレートBEE:ベンゾインエチルエーテル
ウレタンアクリレート1:ヘキサメチレンジイソシアネートを3量化して得られるトリイソシアネート1モルに対して3−アクリロイルオキシ−2−ヒドロキシプロピルメタクリレート3モルを反応して得られるウレタン化合物
DEMA:ジエチルアミノエチルメタアクリレート
シリカ微粒子1:シリカ微粒子(平均粒子径10nm)
IPA:イソプロピルアルコール
PGM:プロピレングリコールモノメチルエーテル
架橋アクリル−スチレン粒子:平均粒径3.5μm、30wt%トルエン分散液(綜研化学(株)製、商品名:SX−350HL)
In the following, abbreviations indicate the following monomers or compounds.
Polyacrylate 1: A mixture of dipentaerythritol hexaacrylate (60 to 70% by mass) and dipentaerythritol pentaacrylate (40 to 30% by mass).
Polyacrylate 2: Mixture of pentaerythritol triacrylate (50 to 70% by mass) and pentaerythritol tetraacrylate (50 to 30% by mass) Diacrylate 1: 1,6-hexanediol diacrylate BEE: Benzoin ethyl ether urethane acrylate 1: Urethane compound DEMA obtained by reacting 3 mol of 3-acryloyloxy-2-hydroxypropyl methacrylate with 1 mol of triisocyanate obtained by trimerization of hexamethylene diisocyanate 1: Silica fine particles (silica fine particles ( (Average particle size 10 nm)
IPA: isopropyl alcohol PGM: propylene glycol monomethyl ether crosslinked acrylic-styrene particles: average particle size 3.5 μm, 30 wt% toluene dispersion (manufactured by Soken Chemical Co., Ltd., trade name: SX-350HL)

開始剤1:2−ヒロドキシ1−1{4−[4−(2−ヒドロキシ−2−メチル−プロピオニル)−ベンジル]フェニル}−2−メチル-プロパン-1-オン
開始剤2:ジフェニル−(2,4,6−トリメチルベンゾイル)フォスフィンオキサイド
開始剤3:ベンゾインエチルエーテル
BYK−UV 3505:アクリル基を有するジメチルポリシロキサン(ビックケミー・ジャパン(株)製、商品名:BYK−UV 3505)
Initiator 1: 2-Hydroxy 1-1 {4- [4- (2-hydroxy-2-methyl-propionyl) -benzyl] phenyl} -2-methyl-propan-1-one
Initiator 2: Diphenyl- (2,4,6-trimethylbenzoyl) phosphine oxide Initiator 3: Benzoin ethyl ether BYK-UV 3505: Dimethylpolysiloxane having an acrylic group (manufactured by Big Chemie Japan Co., Ltd., trade name: BYK-UV 3505)

転写フィルム1:帯電防止層を積層した転写フィルム
転写フィルム2:反射防止転写フィルム(尾池工業(株)製、商品名:STEP PAR−1)(PETフィルム、剥離層、反射防止層、硬化塗膜層、接着層の順に積層された積層フイルム)
Transfer film 1: Transfer film laminated with antistatic layer Transfer film 2: Antireflection transfer film (Oike Industry Co., Ltd., trade name: STEP PAR-1) (PET film, release layer, antireflection layer, cured coating) (Laminated film laminated in order of film layer and adhesive layer)

[製造例1]硬化性組成物(a)の調製
硬化被膜(A)を形成するための硬化性組成物(a)を、次の手順により調製した。ポリアクリレート1を20質量部、ポリアクリレート2を45質量部、ジアクリレート1を35部質量及び開始剤3を1.5質量部を混合し、これを硬化性組成物(a)とした。
[Production Example 1] Preparation of curable composition (a) A curable composition (a) for forming a cured film (A) was prepared by the following procedure. 20 parts by mass of polyacrylate 1, 45 parts by mass of polyacrylate 2, 35 parts by mass of diacrylate 1 and 1.5 parts by mass of initiator 3 were mixed to obtain a curable composition (a).

[製造例2]帯電防止化合物の合成
撹拌羽根付きガラス製フラスコに、ジメチルアミノプロピルメタクリルアミド188質量部、メタノール228質量部を投入し、撹拌しながらジメチル硫酸136質量部、メタノール41.3質量部の混合物を、フラスコ内の反応溶液の温度が15℃以下を維持するように制御しながら滴下した。滴下を終了した後、さらに30分間撹拌を続け、四級アンモニウム塩基を有する化合物溶液を得た。
[Production Example 2] Synthesis of antistatic compound A glass flask equipped with stirring blades was charged with 188 parts by mass of dimethylaminopropylmethacrylamide and 228 parts by mass of methanol, and 136 parts by mass of dimethyl sulfate and 41.3 parts by mass of methanol while stirring. Was added dropwise while controlling so that the temperature of the reaction solution in the flask was maintained at 15 ° C. or lower. After completion of the dropwise addition, stirring was further continued for 30 minutes to obtain a compound solution having a quaternary ammonium base.

この化合物溶液に2,2−アゾビス(2,4−ジメチルバレロニトリル)2.4質量部、n−オクチルメルカプタン2.4質量部、メタノール384質量部、ポリエチレングリコール(23)モノメタクリレートモノメチルエーテル(カッコ内はポリエチレングリコールユニットの数)485質量部を加え、窒素雰囲気下、60℃で6時間重合させた。次いで、得られた化合物を取り出し、50℃で3日間真空乾燥して、帯電防止性を付与する帯電防止化合物を得た。   In this compound solution, 2.4 parts by mass of 2,2-azobis (2,4-dimethylvaleronitrile), 2.4 parts by mass of n-octyl mercaptan, 384 parts by mass of methanol, polyethylene glycol (23) monomethacrylate monomethyl ether (parentheses) The inside was 485 parts by mass of the number of polyethylene glycol units) and polymerized at 60 ° C. for 6 hours in a nitrogen atmosphere. Subsequently, the obtained compound was taken out and vacuum-dried at 50 ° C. for 3 days to obtain an antistatic compound imparting antistatic properties.

[製造例3]帯電防止層を積層した転写フィルム1の製造
以下の手順で帯電防止層を積層した転写フィルムを作成した。厚み50μmのPETフィルム「OX−50」(帝人デュポンフィルム(株)製、商品名)の高平滑面上に、ELCOM MR1008SBC(日揮触媒化成(株)製、商品名)を乾燥後の膜厚が1.2μmになるようにバーコーターを用いてコートした後、100℃で5分間乾燥して、PETフィルムの表面に帯電防止層を形成し、これを転写フイルム1とした。
[Production Example 3] Production of transfer film 1 with an antistatic layer laminated A transfer film with an antistatic layer laminated was prepared by the following procedure. The film thickness after drying ELCOM MR1008SBC (manufactured by JGC Catalysts & Chemicals Co., Ltd., trade name) on a highly smooth surface of a PET film “OX-50” (trade name, manufactured by Teijin DuPont Films Co., Ltd.) having a thickness of 50 μm After coating with a bar coater so as to have a thickness of 1.2 μm, the film was dried at 100 ° C. for 5 minutes to form an antistatic layer on the surface of the PET film.

[製造例4] 樹脂基材の原料(Z)の調整
質量平均分子量22万のポリメタクリル酸メチル20質量部及びメタクリル酸メチル80部を含有する混合物を100質量部、2−(5−メチル−2−ヒドロキシフェニル)−ベンゾトリアゾール0.01質量部、アゾビスジメチルバレロニトリル0.05質量部、ジオクチルスルフォサクシネートのナトリウム塩0.005質量部を含有する混合液を調整した後、減圧下での溶存空気を除去して、これを樹脂基材の原料(Z)とした。
[Production Example 4] 100 parts by weight of a mixture containing 20 parts by weight of polymethyl methacrylate and 80 parts by weight of methyl methacrylate having an adjusted weight average molecular weight of 220,000 of the resin base material (Z), 2- (5-methyl- After adjusting a mixed solution containing 0.01 part by mass of 2-hydroxyphenyl) -benzotriazole, 0.05 part by mass of azobisdimethylvaleronitrile, and 0.005 part by mass of sodium salt of dioctylsulfosuccinate, The dissolved air was removed and used as a raw material (Z) for the resin base material.

〔実施例1〕
鏡面を有するSUS304板を鋳型として用いた。この鋳型の鏡面上に、製造例1で調整した硬化性組成物(a)を塗布し、厚さ12μmのPETフィルムを被せた。塗布した硬化性組成物(a)の塗膜を硬化前被膜(A−1)とよぶ。
[Example 1]
A SUS304 plate having a mirror surface was used as a mold. On the mirror surface of this mold, the curable composition (a) prepared in Production Example 1 was applied and covered with a PET film having a thickness of 12 μm. The coating film of the applied curable composition (a) is referred to as a pre-curing film (A-1).

前記硬化前被膜(A−1)のPETフィルムの表面に、JIS硬度40°のゴムロールを圧着させて、気泡を含まないように過剰な硬化性組成物(a)をしごき出し、前記鋳型の表面に硬化前被膜(A−2)の塗膜を形成した。次いで、硬化前被膜(A−2)の塗膜が形成された前記鋳型を、PETフィルムが上側になるようにして、出力40Wの蛍光紫外線ランプ(東芝(株)製、商品名:FL40BL)の下方20cmの位置を、2m/分間のスピードで通過させて、PETフィルムを介して蛍光紫外線ランプの光を硬化前被膜(A−2)に照射して、硬化させて、硬化後被膜(A−3)を得た。次いで、硬化後被膜(A−3)からPETフィルムを剥離し、硬化被膜(A−4)が積層された鋳型を得た。   A rubber roll having a JIS hardness of 40 ° is pressure-bonded to the surface of the PET film of the pre-curing coating (A-1), and the excess curable composition (a) is squeezed out so as not to contain air bubbles. A film of the pre-curing coating (A-2) was formed. Next, the mold on which the pre-curing coating (A-2) was formed was placed on the fluorescent UV lamp (trade name: FL40BL, manufactured by Toshiba Corporation) with an output of 40 W with the PET film on the upper side. A position 20 cm below is passed through at a speed of 2 m / min, and the film before curing (A-2) is irradiated with the light of the fluorescent ultraviolet lamp through the PET film to be cured, and the film after curing (A- 3) was obtained. Next, the PET film was peeled from the coated film (A-3) after curing to obtain a mold on which the cured film (A-4) was laminated.

次いで、硬化被膜(A−4)が積層された鋳型の硬化被膜部分を上側にして、出力30W/cm2の高圧水銀灯の下方20cmの位置を3m/分間のスピードで通過させて、硬化被膜(A−4)に紫外線を照射してさらに硬化させ、膜厚30μmの硬化被膜(A−4)が鋳型表面に積層された積層型(X)を得た。硬化被膜(A−4)の鉛筆硬度は8Hであった。 Next, with the cured coating portion of the mold on which the cured coating (A-4) was laminated facing upward, a position 20 cm below the high-pressure mercury lamp with an output of 30 W / cm 2 was passed at a speed of 3 m / min, and the cured coating ( A-4) was further cured by irradiating with ultraviolet rays to obtain a laminated mold (X) in which a cured film (A-4) having a film thickness of 30 μm was laminated on the mold surface. The pencil hardness of the cured coating (A-4) was 8H.

次いで、前記積層型(X)と、硬化被膜(A−4)を形成していない別のSUS304板とを、積層型(X)の硬化被膜(A−4)が内側になるように対向させて、これら2枚のSUS304板の周縁部を軟質ポリ塩化ビニル製のガスケットで封じて、積層鋳型(Y)を作製した。   Next, the laminated mold (X) and another SUS304 plate not formed with the cured film (A-4) are opposed to each other so that the cured film (A-4) of the laminated mold (X) is on the inside. Then, the peripheral portions of these two SUS304 plates were sealed with a gasket made of soft polyvinyl chloride to produce a laminated mold (Y).

製造例4で調整した樹脂基材の原料(Z)を、前記の積層鋳型(Y)内に注入して軟質ポリ塩化ビニル製のガスケットで完全に封止した後、80℃の水浴中で1時間、次いで130℃の空気炉中で1時間加熱して重合させた。次いで、積層鋳型(Y)を室温まで冷却した後、両側2枚のSUS304板を剥離して、樹脂基材の片側表面に硬化被膜(A−4)が形成された厚さ1mmの樹脂積層体(C−1)を得た。   The resin base material (Z) prepared in Production Example 4 was injected into the laminated mold (Y) and completely sealed with a soft polyvinyl chloride gasket, and then 1 in an 80 ° C. water bath. Polymerization was carried out by heating for 1 hour in an air furnace at 130 ° C. for 1 hour. Next, after cooling the laminated mold (Y) to room temperature, the two SUS304 plates on both sides were peeled off, and a 1 mm thick resin laminate in which a cured coating (A-4) was formed on one surface of the resin substrate (C-1) was obtained.

ポリアクリレート1を42.5質量部、ポリアクリレート2を42.5質量部、DEMAを5 質量部、トルエンを474質量部、酢酸エチルを237質量部、IPAを237質量部、架橋アクリル−スチレン粒子(固形分)を10質量部、開始剤1を5質量部及びBYK−UV 3505を混合し、これを硬化性組成物(s1)とした。前記樹脂積層体(C−1)の硬化被膜(A−4)が形成された面に、前記硬化性組成物(s1)をバーコーターを用いて塗布し、これを樹脂積層体(C−2)とした。   42.5 parts by mass of polyacrylate 1, 42.5 parts by mass of polyacrylate 2, 5 parts by mass of DEMA, 474 parts by mass of toluene, 237 parts by mass of ethyl acetate, 237 parts by mass of IPA, crosslinked acrylic-styrene particles 10 parts by mass (solid content), 5 parts by mass of initiator 1 and BYK-UV 3505 were mixed to obtain a curable composition (s1). The said curable composition (s1) is apply | coated to the surface in which the cured film (A-4) of the said resin laminated body (C-1) was formed using a bar-coater, This is resin laminated body (C-2) ).

次いで、前記樹脂積層体(C−2)を70℃の熱風乾燥炉で10分間乾燥した後、高圧水銀灯を用いて積算光量600mJ/cm2(波長320〜380nmの紫外線エネルギー量)の紫外線を照射して、膜厚1.3μmの硬化被膜を有する樹脂積層体(C−3)を得た。 Subsequently, after drying the said resin laminated body (C-2) for 10 minutes with a 70 degreeC hot air drying furnace, it irradiates the ultraviolet-ray of the integrated light quantity 600mJ / cm < 2 > (wavelength energy amount of 320-380 nm) using a high pressure mercury lamp. And the resin laminated body (C-3) which has a cured film with a film thickness of 1.3 micrometers was obtained.

得られた樹脂積層体(C−3)について、全光線透過率、ヘイズ値、鉛筆硬度、接触角、硬化被膜の残存率及び防汚耐久性を評価した。評価結果を表3に示す。   About the obtained resin laminated body (C-3), the total light transmittance, the haze value, pencil hardness, the contact angle, the residual rate of the cured film, and antifouling durability were evaluated. The evaluation results are shown in Table 3.

得られた樹脂積層体(C−3)は、表面の鉛筆硬度が8Hであり、透明性、表面硬度、硬化被膜(A)と硬化被膜(B)の密着性に優れていた。また、耐擦傷性及び耐クラック性が良好であった。   The obtained resin laminate (C-3) had a surface pencil hardness of 8H, and was excellent in transparency, surface hardness, and adhesion between the cured coating (A) and the cured coating (B). Further, the scratch resistance and crack resistance were good.

[実施例2〜9]
硬化性組成物(s1)として表1記載の組成物(1〜7)を使用した。硬化被膜(A)の膜厚、硬化被膜(B‘)の組成又は膜厚を表3記載のとおりとした以外は、実施例1と同様の方法で樹脂積層体を得た。評価結果を表3に示す。
[Examples 2 to 9]
The composition (1-7) of Table 1 was used as a curable composition (s1). A resin laminate was obtained in the same manner as in Example 1 except that the film thickness of the cured film (A), the composition of the cured film (B ′), or the film thickness was as described in Table 3. The evaluation results are shown in Table 3.

[比較例1]
硬化性組成物(s1)の組成物の種類、硬化被膜(A)の膜厚、硬化被膜(B)の組成と膜厚を表3記載のとおりとした以外は、実施例1と同様の方法で樹脂積層体を得た。評価結果を表3に示す。比較例1の樹脂積層体は、硬化性組成物(s1)に含まれる有機溶媒(b4)がPGMであり、硬化性組成物(s1)が(b2−1)成分と(b2−2)成分を含まないため、鉛筆硬度、耐擦傷性、耐クラック製、硬化被膜の残存率が不十分であった。
[Comparative Example 1]
The same method as in Example 1 except that the type of composition of the curable composition (s1), the film thickness of the cured film (A), and the composition and film thickness of the cured film (B) were as shown in Table 3. A resin laminate was obtained. The evaluation results are shown in Table 3. In the resin laminate of Comparative Example 1, the organic solvent (b4) contained in the curable composition (s1) is PGM, and the curable composition (s1) is the components (b2-1) and (b2-2). Thus, the pencil hardness, scratch resistance, crack resistance, and the residual rate of the cured film were insufficient.

[実施例10]
硬化被膜(A)の膜厚を表1記載のとおりとした以外は、実施例1と同様の方法で樹脂積層体を得た。評価結果を表3に示す。環境試験後の硬化被膜の残存率と耐クラック性が不十分であった。
[Example 10]
A resin laminate was obtained in the same manner as in Example 1 except that the thickness of the cured coating (A) was as shown in Table 1. The evaluation results are shown in Table 3. The residual rate and crack resistance of the cured film after the environmental test were insufficient.

[比較例2]
硬化被膜(A)を形成しない以外は、実施例1と同様の方法で樹脂積層体を得た。評価結果を表3に示す。比較例3の樹脂積層体は、硬化被膜(A)がないため、耐擦傷性、鉛筆硬度が不十分であった。
[Comparative Example 2]
A resin laminate was obtained in the same manner as in Example 1 except that the cured film (A) was not formed. The evaluation results are shown in Table 3. Since the resin laminate of Comparative Example 3 had no cured coating (A), the scratch resistance and pencil hardness were insufficient.

[実施例11]
実施例1で作成した樹脂積層体(C−1)の硬化被膜(A)が形成された面に、硬化性組成物(s2)として、表2記載の組成物9を塗布した。
[Example 11]
The composition 9 shown in Table 2 was applied as a curable composition (s2) to the surface on which the cured film (A) of the resin laminate (C-1) prepared in Example 1 was formed.

次いで、前記樹脂積層体(C−1)の組成物9の塗布面に、製造例3で作成した転写フィルム1の帯電防止層が形成された面を、接触するように貼り合わせ、プレスロールの下を2.5m/分の速度で通過させて、前記硬化前被膜(B−1)の膜厚が表4記載のとおりとなるように調整しながら積層することにより、樹脂積層体(D−1)、硬化前被膜(B−1)、転写フィルム1の帯電防止層が順次積層された樹脂積層体(D−2)を得た。得られた樹脂積層体(D−2)を1分間保持した後、樹脂積層体(D−2)を出力120W/cmのメタルハライドランプの下24cmの位置を2.5m/分の速度で通過させて、メタルハライドランプの光を、硬化前被膜(B−1)に、転写フィルム1を介して照射して、硬化させることにより硬化被膜(B´´)を形成して、樹脂積層体(D−3)を得た。   Next, the surface on which the antistatic layer of the transfer film 1 prepared in Production Example 3 was formed was bonded to the application surface of the composition 9 of the resin laminate (C-1) so as to be in contact with the press roll. By passing through the bottom at a speed of 2.5 m / min and laminating while adjusting the film thickness of the pre-curing coating (B-1) as shown in Table 4, the resin laminate (D- 1) A resin laminate (D-2) in which the pre-curing coating (B-1) and the antistatic layer of the transfer film 1 were sequentially laminated was obtained. After the obtained resin laminate (D-2) is held for 1 minute, the resin laminate (D-2) is passed through a position 24 cm below the metal halide lamp with an output of 120 W / cm at a speed of 2.5 m / min. The cured film (B ″) is formed by irradiating the cured film (B-1) with light from the metal halide lamp through the transfer film 1 and curing it, and the resin laminate (D− 3) was obtained.

この後、転写フィルム1のPETフィルムを前記の樹脂積層体(D−3)から剥離し、樹脂積層体(D−4)を得た。得られた樹脂積層体(D−4)の評価結果を表4に示す。   Thereafter, the PET film of the transfer film 1 was peeled from the resin laminate (D-3) to obtain a resin laminate (D-4). Table 4 shows the evaluation results of the obtained resin laminate (D-4).

[実施例12〜16]
硬化性組成物(s2)として表2記載の組成物(10〜12)を使用した。転写フィルムの種類又は硬化被膜(B´´)の膜厚を表4記載のとおりとした以外は、実施例10と同様の方法で樹脂積層体を得た。得られた樹脂積層体の評価結果を表4に示す。
[Examples 12 to 16]
The composition (10-12) of Table 2 was used as a curable composition (s2). A resin laminate was obtained in the same manner as in Example 10, except that the type of transfer film or the film thickness of the cured coating (B ″) was as shown in Table 4. Table 4 shows the evaluation results of the obtained resin laminate.

[比較例3,4]
硬化性組成物(s2)として表2の組成物(13,14)を使用し、さらに転写フィルムの種類又は硬化被膜(B´´)の膜厚を表4記載のとおりとした以外は、実施例12と同様の方法で樹脂積層体を得た。なお、転写フイルム2を使用したときは、転写フイルム2の接着層が硬化被膜(B)に接するように積層した。得られた樹脂積層体の評価結果を表4に示す。硬化性組成物(s2)が(b2−1)成分と(b2−2)成分を含まないため、鉛筆硬度、耐擦傷性、硬化被膜の残存率が不十分であった。また、比較例4は硬化被膜(B´´)の膜厚が大きいため、機能層(C)との密着性が不十分であった。
[Comparative Examples 3 and 4]
Implemented except that the composition (13, 14) in Table 2 was used as the curable composition (s2), and the type of transfer film or the film thickness of the cured coating (B ″) was as described in Table 4. A resin laminate was obtained in the same manner as in Example 12. When the transfer film 2 was used, the transfer film 2 was laminated so that the adhesive layer of the transfer film 2 was in contact with the cured film (B). Table 4 shows the evaluation results of the obtained resin laminate. Since the curable composition (s2) does not contain the component (b2-1) and the component (b2-2), the pencil hardness, the scratch resistance, and the residual ratio of the cured film were insufficient. Moreover, since the comparative example 4 had a large film thickness of the cured coating (B ″), the adhesion with the functional layer (C) was insufficient.




Claims (22)

樹脂基材の少なくとも一方の表面に硬化被膜(A)を備え、前記硬化被膜(A)における樹脂基材と接する面と対向する面に硬化被膜(B)を備えたシート状の樹脂積層体であって、
前記硬化被膜(A)の鉛筆硬度が8H以上であり、
前記硬化被膜(B)がウレタン(メタ)アクリレート由来の繰り返し単位(b2−1)及びアミノ基を有する(メタ)アクリレート由来の繰り返し単位(b2−2)の少なくとも1種類を含む、樹脂積層体。
A sheet-like resin laminate comprising a cured coating (A) on at least one surface of a resin substrate, and a cured coating (B) on the surface facing the resin substrate in the cured coating (A). There,
The cured coating (A) has a pencil hardness of 8H or more,
The resin laminated body in which the said cured film (B) contains at least 1 type of the repeating unit (b2-2) derived from the repeating unit (b2-1) derived from urethane (meth) acrylate and the (meth) acrylate which has an amino group.
前記硬化被膜(A)の膜厚が17μm以上40μm以下である、請求項1に記載の樹脂積層体。   The resin laminate according to claim 1, wherein the thickness of the cured coating (A) is 17 µm or more and 40 µm or less. 前記樹脂積層体の表面の鉛筆硬度が8H以上である、請求項1又は2に記載の樹脂積層体。   The resin laminate according to claim 1 or 2, wherein the surface of the resin laminate has a pencil hardness of 8H or more. 前記樹脂積層体において、ISO 2409:1992に準拠したクロスカット剥離試験による前記硬化被膜(B)の残存率が80%以上である、請求項1〜3のいずれかに記載の樹脂積層体。   The resin laminate according to any one of claims 1 to 3, wherein in the resin laminate, a residual ratio of the cured film (B) by a cross-cut peel test based on ISO 2409: 1992 is 80% or more. 前記硬化被膜(B)が、低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層から選ばれる少なくとも1つの機能を有する層からなる、請求項1〜4のいずれかに記載の樹脂積層体。   The cured film (B) is composed of a layer having at least one function selected from a low refractive index layer, a high refractive index layer, a hard coat layer, an antistatic layer, an antiglare layer and an antifouling layer. 4. The resin laminate according to any one of 4 above. 請求項1又は2に記載の樹脂積層体の硬化被膜(B)の表面に機能層(C)が積層されたシート状の樹脂積層体であって、
前記機能層(C)が、低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層から選ばれる少なくとも1つの機能を有する層からなる、樹脂積層体。
A sheet-like resin laminate in which the functional layer (C) is laminated on the surface of the cured coating (B) of the resin laminate according to claim 1 or 2,
A resin laminate comprising the functional layer (C) comprising a layer having at least one function selected from a low refractive index layer, a high refractive index layer, a hard coat layer, an antistatic layer, an antiglare layer and an antifouling layer.
前記樹脂積層体の表面の鉛筆硬度が8H以上である、請求項6に記載の樹脂積層体。   The resin laminate according to claim 6, wherein the surface of the resin laminate has a pencil hardness of 8H or more. 前記樹脂積層体において、ISO 2409:1992に準拠したクロスカット剥離試験による前記硬化被膜(B)および前記機能層(C)の残存率が80%以上である、請求項6又は7に記載の樹脂積層体。   The resin according to claim 6 or 7, wherein in the resin laminate, a residual ratio of the cured film (B) and the functional layer (C) by a cross-cut peel test in conformity with ISO 2409: 1992 is 80% or more. Laminated body. 樹脂基材の少なくとも一方の表面に硬化被膜(A)を備え、硬化被膜(A)における樹脂基材と接する面と対向する面に硬化被膜(B)を備えたシート状の樹脂積層体であって、
硬化被膜(A)が、分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(a1)、分子中に2個以下の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(a2)を含み、
硬化被膜(B)が、ウレタン(メタ)アクリレート由来の繰り返し単位(b2−1)及びアミノ基を有する(メタ)アクリレート由来の繰り返し単位(b2−2)の少なくとも1種類を含む、樹脂積層体。
A sheet-like resin laminate comprising a cured coating (A) on at least one surface of a resin substrate, and a cured coating (B) on the surface facing the resin substrate in the cured coating (A). And
The cured film (A) has a repeating unit (a1) derived from a monomer having 3 or more (meth) acryloyloxy groups in the molecule, and a single amount having 2 or less (meth) acryloyloxy groups in the molecule Including a repeating unit (a2) derived from a body,
The resin laminate, wherein the cured coating (B) includes at least one of a repeating unit (b2-1) derived from urethane (meth) acrylate and a repeating unit (b2-2) derived from (meth) acrylate having an amino group.
前記硬化被膜(A)の鉛筆硬度が8H以上である、請求項9に記載の樹脂積層体。   The resin laminate according to claim 9, wherein the cured film (A) has a pencil hardness of 8H or more. 前記硬化被膜(A)の膜厚が17μm以上40μm以下である、請求項9又は10に記載の樹脂積層体。   The resin laminated body of Claim 9 or 10 whose film thickness of the said cured film (A) is 17 micrometers or more and 40 micrometers or less. 前記樹脂積層体の表面の鉛筆硬度が8H以上である、請求項9〜11のいずれかに記載の樹脂積層体。   The resin laminate according to any one of claims 9 to 11, wherein the surface of the resin laminate has a pencil hardness of 8H or more. 請求項9〜12のいずれかに記載の樹脂積層体であって、
前記硬化被膜(B)が、分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(b1)を含み、且つ、低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層から選ばれる少なくとも1つの機能を有する層からなる硬化被膜(B´)である樹脂積層体。
The resin laminate according to any one of claims 9 to 12,
The cured coating (B) contains a repeating unit (b1) derived from a monomer having three or more (meth) acryloyloxy groups in the molecule, and a low refractive index layer, a high refractive index layer, a hard coat A resin laminate which is a cured coating (B ′) comprising a layer having at least one function selected from a layer, an antistatic layer, an antiglare layer and an antifouling layer.
前記硬化被膜(B´)の膜厚が0.6μm以上3μm以下である、請求項13に記載の樹脂積層体。   The resin laminated body of Claim 13 whose film thickness of the said cured film (B ') is 0.6 micrometer or more and 3 micrometers or less. 請求項9〜11のいずれかに記載の樹脂積層体の硬化被膜(B)の表面に、機能層(C)を備えた樹脂積層体であって、
前記硬化被膜(B)が、分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(b1)を含む樹脂組成物からなる硬化被膜(B´´)であり、
前記機能層(C)が、低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層から選ばれる少なくとも1つの機能を有する層からなる、樹脂積層体。
A resin laminate comprising a functional layer (C) on the surface of the cured coating (B) of the resin laminate according to any one of claims 9 to 11,
The cured coating (B) is a cured coating (B ″) made of a resin composition containing a repeating unit (b1) derived from a monomer having 3 or more (meth) acryloyloxy groups in the molecule,
A resin laminate comprising the functional layer (C) comprising a layer having at least one function selected from a low refractive index layer, a high refractive index layer, a hard coat layer, an antistatic layer, an antiglare layer and an antifouling layer.
前記硬化被膜(B´´)が無機微粒子(b3)を含む、請求項15に記載の樹脂積層体。   The resin laminate according to claim 15, wherein the cured coating (B ″) contains inorganic fine particles (b3). 前記硬化被膜(B´´)の膜厚が3μm以上7μm以下である、請求項15に記載の樹脂積層体。   The resin laminate according to claim 15, wherein a film thickness of the cured coating (B ″) is 3 μm or more and 7 μm or less. 前記機能層(C)の膜厚が0.05μm以上5.0μm以下である、請求項15に記載の樹脂積層体。   The resin laminate according to claim 15, wherein the functional layer (C) has a thickness of 0.05 μm or more and 5.0 μm or less. 下記工程(1)及び(2)を含む樹脂積層体の製造方法。
工程(1):樹脂基材の少なくとも一方の表面に、
分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(a1)、分子中に2個以下の(メタ)アクリロイルオキシ基を有する単量体由来の繰り返し単位(a2)を含む硬化被膜(A)を形成する。
工程(2):前記硬化被膜(A)の表面に、ウレタン(メタ)アクリレート単位(b2−1)及びアミノ基を有するメタクリレート単位(b2−2)の少なくとも1種類を含む硬化被膜(B)を形成する。
The manufacturing method of the resin laminated body containing following process (1) and (2).
Step (1): on at least one surface of the resin base material,
Repeating unit (a1) derived from a monomer having 3 or more (meth) acryloyloxy groups in the molecule, repeating unit (a2) derived from a monomer having 2 or less (meth) acryloyloxy groups in the molecule ) Is formed.
Step (2): A cured film (B) containing at least one kind of urethane (meth) acrylate unit (b2-1) and methacrylate unit (b2-2) having an amino group on the surface of the cured film (A). Form.
前記工程(2)の硬化被膜(B)を形成する工程が、前記硬化被膜(A)の表面に、
・分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体(b1)と、
・ウレタン(メタ)アクリレート単量体(b2−1)及びアミノ基を有する(メタ)アクリレート単量体(b2−2)の少なくとも1種類(ただし、単量体(b1)を除く)と、
・有機溶剤(b4)
を含む硬化性組成物(s1)の塗膜を形成し、硬化して、硬化被膜(B´)を形成することを含む、請求項19に記載の樹脂積層体の製造方法。
The step of forming the cured coating (B) in the step (2) is performed on the surface of the cured coating (A).
A monomer (b1) having 3 or more (meth) acryloyloxy groups in the molecule;
At least one of the urethane (meth) acrylate monomer (b2-1) and the (meth) acrylate monomer (b2-2) having an amino group (excluding the monomer (b1));
・ Organic solvent (b4)
The manufacturing method of the resin laminated body of Claim 19 including forming the coating film of the curable composition (s1) containing this, hardening, and forming a cured coating film (B ').
前記工程(2)の硬化被膜(B)を形成する工程が、前記硬化被膜(A)の表面に、
・分子中に3個以上の(メタ)アクリロイルオキシ基を有する単量体(b1)、及び
・ウレタン(メタ)アクリレート単量体(b2−1)及びアミノ基を有する(メタ)アクリレート単量体(b2−2)の少なくとも1種類(ただし、単量体(b1)を除く)
を含む硬化性組成物(s2)の塗膜を形成し、硬化して、硬化被膜(B´´)を形成することを含み、さらに工程(2)の後に、下記工程(3)〜(5)を行うことを含む、請求項19に記載の樹脂積層体の製造方法。
工程(3):樹脂フィルムの表面に、低屈折率層、高屈折率層、ハードコート層、帯電防止層、防眩層及び防汚層から選ばれる少なくとも1つの機能を有する層からなる、機能層(C)を形成する。
工程(4):前記工程(2)で得られた硬化被膜(B´´)の表面に、前記工程(3)の機能層(C)を貼り合わせる。
工程(5):前記樹脂フィルムを剥離し、樹脂基材の少なくとも一方の表面に、前記硬化被膜(A)、前記硬化被膜(B´´)、前記機能層(C)が順次積層された樹脂積層体を得る。
The step of forming the cured coating (B) in the step (2) is performed on the surface of the cured coating (A).
A monomer (b1) having 3 or more (meth) acryloyloxy groups in the molecule, and a urethane (meth) acrylate monomer (b2-1) and a (meth) acrylate monomer having an amino group At least one type of (b2-2) (excluding the monomer (b1))
Forming a cured coating film of the curable composition (s2) containing, and curing to form a cured coating film (B ″), and further after the step (2), the following steps (3) to (5) The manufacturing method of the resin laminated body of Claim 19 including performing this.
Step (3): a function comprising a layer having at least one function selected from a low refractive index layer, a high refractive index layer, a hard coat layer, an antistatic layer, an antiglare layer and an antifouling layer on the surface of the resin film Layer (C) is formed.
Step (4): The functional layer (C) of the step (3) is bonded to the surface of the cured film (B ″) obtained in the step (2).
Step (5): A resin in which the resin film is peeled and the cured coating (A), the cured coating (B ″), and the functional layer (C) are sequentially laminated on at least one surface of a resin base material. A laminate is obtained.
前記工程(3)において、前記機能層(C)の膜厚が0.05μm以上5.0μm以下となるように機能層(C)を形成する、請求項21に記載の樹脂積層体の製造方法。

The method for producing a resin laminate according to claim 21, wherein in the step (3), the functional layer (C) is formed so that the film thickness of the functional layer (C) is 0.05 µm or more and 5.0 µm or less. .

JP2015235714A 2015-12-02 2015-12-02 Resin laminate and method for producing the same Pending JP2017100366A (en)

Priority Applications (1)

Application Number Priority Date Filing Date Title
JP2015235714A JP2017100366A (en) 2015-12-02 2015-12-02 Resin laminate and method for producing the same

Applications Claiming Priority (1)

Application Number Priority Date Filing Date Title
JP2015235714A JP2017100366A (en) 2015-12-02 2015-12-02 Resin laminate and method for producing the same

Publications (1)

Publication Number Publication Date
JP2017100366A true JP2017100366A (en) 2017-06-08

Family

ID=59015308

Family Applications (1)

Application Number Title Priority Date Filing Date
JP2015235714A Pending JP2017100366A (en) 2015-12-02 2015-12-02 Resin laminate and method for producing the same

Country Status (1)

Country Link
JP (1) JP2017100366A (en)

Cited By (2)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
JP2023176183A (en) * 2022-05-31 2023-12-13 株式会社ネオス Curable composition and film containing cured layer thereof
CN119421788A (en) * 2022-07-01 2025-02-11 三菱化学株式会社 Laminated Film

Citations (14)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
JP2008116596A (en) * 2006-11-02 2008-05-22 Riken Technos Corp Hard coat film and antireflection film
JP2009072954A (en) * 2007-09-19 2009-04-09 Toppan Printing Co Ltd Antiglare sheet for transfer
JP2009073873A (en) * 2007-09-19 2009-04-09 Toray Ind Inc Curable resin composition for molding die, method for producing mold, method for producing structure, and method for producing member for display
JP2009086361A (en) * 2007-09-28 2009-04-23 Dainippon Printing Co Ltd Anti-glare film
WO2011065252A1 (en) * 2009-11-30 2011-06-03 電気化学工業株式会社 Adhesive sheet and electronic component
JP2014102320A (en) * 2012-11-19 2014-06-05 Toppan Printing Co Ltd Optical hard coat material
JP2014151588A (en) * 2013-02-12 2014-08-25 Nippon Synthetic Chem Ind Co Ltd:The Laminate and use thereof
JP2014206707A (en) * 2013-04-16 2014-10-30 凸版印刷株式会社 Optical hard coat material and display device
JP2014238614A (en) * 2013-01-11 2014-12-18 大日本印刷株式会社 Hard coat film, curable resin composition for hard coat layer, and method for producing hard coat film
WO2015076566A1 (en) * 2013-11-19 2015-05-28 주식회사 엘지화학 Plastic film
WO2015093404A1 (en) * 2013-12-19 2015-06-25 三菱レイヨン株式会社 Resin laminate and production method therefor
JP2015199333A (en) * 2014-03-31 2015-11-12 三菱化学株式会社 Laminated body
WO2015182744A1 (en) * 2014-05-30 2015-12-03 三菱レイヨン株式会社 Resin product
JP2016538159A (en) * 2013-11-19 2016-12-08 エルジー・ケム・リミテッド Plastic film

Patent Citations (14)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
JP2008116596A (en) * 2006-11-02 2008-05-22 Riken Technos Corp Hard coat film and antireflection film
JP2009072954A (en) * 2007-09-19 2009-04-09 Toppan Printing Co Ltd Antiglare sheet for transfer
JP2009073873A (en) * 2007-09-19 2009-04-09 Toray Ind Inc Curable resin composition for molding die, method for producing mold, method for producing structure, and method for producing member for display
JP2009086361A (en) * 2007-09-28 2009-04-23 Dainippon Printing Co Ltd Anti-glare film
WO2011065252A1 (en) * 2009-11-30 2011-06-03 電気化学工業株式会社 Adhesive sheet and electronic component
JP2014102320A (en) * 2012-11-19 2014-06-05 Toppan Printing Co Ltd Optical hard coat material
JP2014238614A (en) * 2013-01-11 2014-12-18 大日本印刷株式会社 Hard coat film, curable resin composition for hard coat layer, and method for producing hard coat film
JP2014151588A (en) * 2013-02-12 2014-08-25 Nippon Synthetic Chem Ind Co Ltd:The Laminate and use thereof
JP2014206707A (en) * 2013-04-16 2014-10-30 凸版印刷株式会社 Optical hard coat material and display device
WO2015076566A1 (en) * 2013-11-19 2015-05-28 주식회사 엘지화학 Plastic film
JP2016538159A (en) * 2013-11-19 2016-12-08 エルジー・ケム・リミテッド Plastic film
WO2015093404A1 (en) * 2013-12-19 2015-06-25 三菱レイヨン株式会社 Resin laminate and production method therefor
JP2015199333A (en) * 2014-03-31 2015-11-12 三菱化学株式会社 Laminated body
WO2015182744A1 (en) * 2014-05-30 2015-12-03 三菱レイヨン株式会社 Resin product

Cited By (3)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
JP2023176183A (en) * 2022-05-31 2023-12-13 株式会社ネオス Curable composition and film containing cured layer thereof
JP7900949B2 (en) 2022-05-31 2026-08-05 株式会社ネオス Curable composition and film containing the cured layer thereof
CN119421788A (en) * 2022-07-01 2025-02-11 三菱化学株式会社 Laminated Film

Similar Documents

Publication Publication Date Title
TWI645963B (en) Resin products
JP5747439B2 (en) Method for continuously producing acrylic resin sheet
KR101578254B1 (en) Method for manufacture of resin laminated body
JP2009157234A (en) Antiglare antireflection film and liquid crystal display provided with the same
JP2010241937A (en) Curable resin composition for hard coat layer, hard coat film, and transmissive optical display device
JP6361506B2 (en) (Meth) acrylic polymer, (meth) acrylic resin composition, (meth) acrylic resin sheet, (meth) acrylic resin laminate and composite sheet
CN105829101A (en) Resin laminate and production method therefor
JP2007030307A (en) Transparent sheet
JP6597302B2 (en) Resin composition, resin sheet, and resin laminate
JP6229204B2 (en) Resin laminate, manufacturing method thereof, and display front plate
JP5594509B2 (en) Laminate and method for producing laminate
JP2019043070A (en) Transfer sheet
CN114651197A (en) Anti-glare film, method for designing anti-glare film, method for manufacturing anti-glare film, optical member, and image display device
JP2005162781A (en) Curable composition and article
JP5601496B2 (en) Method for producing silica sol for coating, coating composition, coating, resin laminate having coating on surface, and method for producing the same
JP6825363B2 (en) Resin laminate and its manufacturing method and glazing for display front plate and mobile body
KR20260032905A (en) Active energy ray curable composition and cured product thereof
JP2006072195A (en) Display surface laminate and its manufacturing method
JP2025149437A (en) Anti-reflection film and image display device using the same

Legal Events

Date Code Title Description
A621 Written request for application examination

Free format text: JAPANESE INTERMEDIATE CODE: A621

Effective date: 20180620

A977 Report on retrieval

Free format text: JAPANESE INTERMEDIATE CODE: A971007

Effective date: 20190225

A131 Notification of reasons for refusal

Free format text: JAPANESE INTERMEDIATE CODE: A131

Effective date: 20190305

A02 Decision of refusal

Free format text: JAPANESE INTERMEDIATE CODE: A02

Effective date: 20190910